Process for preparation of solid catalyst molded bodies for gas phase oxidation of olefins and / or alcohols to alpha, beta-unsaturated aldehydes and / or alpha, beta-unsaturated carboxylic acids
By controlling the density and heat treatment conditions of the catalyst molded body, the problem of poor catalyst performance in the prior art is solved, and higher valuable product selectivity and yield are achieved.
Patent Information
- Application Number
- CN202380059898.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-16
- Filing Date
- 2023-08-07
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art fails to effectively utilize pressure and heat treatment conditions when preparing catalyst molded bodies for gas phase oxidation, resulting in poor selectivity and yield of valuable products.
When preparing the catalyst molded body, the density of the precursor molded body is controlled to be between 1.70 g/cm3 and 2.30 g/cm3, and a weight loss of 25% to 40% is achieved during the heat treatment process, a solid catalyst molded body with excellent catalytic properties is formed.
The valuable product selectivity and yield of the catalyst are improved, especially in the gas-phase oxidation reaction of olefins and alcohols, which significantly improve the generation efficiency of α,β-unsaturated aldehydes and α,β-unsaturated carboxylic acids.
Smart Images

Figure BDA0005272064250000501 
Figure BDA0005272064250000511 
Figure BDA0005272064250000521
Abstract
Description
[0001] This invention relates to a method for preparing a solid catalyst mold for the gas-phase oxidation of olefins and / or alcohols to α,β-unsaturated aldehydes and / or α,β-unsaturated carboxylic acids, wherein a density of 1.20 g / cm³ is prepared by compression. 3 Up to 1.70 g / cm 3 The precursor molded body is heat-treated, and the weight loss during the heat treatment is 25% to 45% by weight.
[0002] The present invention also relates to a solid catalyst molded body obtainable according to the invention and its use in multiphase catalytic partial gas-phase oxidation in a catalyst fixed bed.
[0003] US2005 / 0065371 describes a catalyst mold containing at least the elements molybdenum, bismuth, and iron for gas-phase oxidation.
[0004] US2006 / 0036111 discloses a gas-phase oxidation method for preparing α,β-unsaturated aldehydes and / or α,β-unsaturated carboxylic acids. The heat loss during calcination must be within specified limits.
[0005] WO 2010 / 000720 teaches a method for preparing solid catalyst molds.
[0006] WO 2013 / 007736 discloses a catalyst mold containing at least the elements molybdenum, bismuth, iron, and cobalt for gas-phase oxidation. The elements bismuth, iron, and cobalt must be present in a specified ratio.
[0007] WO 2015 / 067659 describes a hollow cylindrical catalyst mold with a defined geometry. The solid catalyst mold exhibits high stability and high selectivity for valuable products in the gas-phase oxidation of propylene to acrolein and acrylic acid.
[0008] WO 2021 / 239483 discloses a solid catalyst molded body with a defined cylindrical structure. The solid catalyst molded body allows for high packing density and low pressure loss in the catalyst fixed bed.
[0009] None of the aforementioned patent applications emphasizes the pressure used in preparing the precursor mold or the density of the precursor mold.
[0010] The object of this invention is to provide an improved method for preparing a solid catalyst for the gas-phase oxidation of olefins and / or alcohols to α,β-unsaturated aldehydes and / or α,β-unsaturated carboxylic acids. The catalyst should exhibit improved selectivity and improved yield of the valuable product. In this context, the valuable product is understood to be the sum of acrolein and acrylic acid.
[0011] The object of this invention is achieved by a method for preparing a solid catalyst mold for the gas-phase oxidation of olefins and / or alcohols to α,β-unsaturated aldehydes and / or α,β-unsaturated carboxylic acids, wherein the solid catalyst mold comprises at least the elements molybdenum, bismuth, iron, cobalt, and optionally nickel.
[0012] a) The aqueous solution or aqueous suspension is produced from each of at least one source of the elemental composition molybdenum, bismuth, iron, cobalt, and optionally at least one source of the elemental composition nickel.
[0013] b) Powder P is produced by drying the aqueous solution or aqueous suspension obtained in a) and optionally pulverizing it.
[0014] c) The powder P obtained in b) is optionally mixed with one or more additives, and after uniform mixing and optional compaction, is compacted into a precursor molded body having a cylindrical structure, and
[0015] d) The precursor molded body obtained in c) is heat-treated to form a solid catalyst molded body.
[0016] The characteristic feature is that the pressure during the compression process in c) is selected such that the density of the precursor molded body is 1.70 g / cm³. 3 Up to 2.30 g / cm 3 , wherein the density of the precursor molded body is the quotient of its mass and geometric volume, and the weight loss during heat treatment in d) is 25 to 40 wt%.
[0017] Geometric volume is the macroscopic volume of the precursor molded body, including holes. For completeness, it should be emphasized that continuous, substantially circular holes and any surface structures such as grooves, notches, or serrations are not part of the macroscopic volume.
[0018] A cylindrical structure is a cylindrical body, preferably having at least one continuous circular opening in the longitudinal direction. In the case of a continuous opening, it is located at the center (hollow cylinder). In the case of multiple continuous openings, these openings are evenly distributed across the cross-section of the cylindrical structure. For example, WO 2021 / 239483 describes a cylindrical structure with three continuous openings.
[0019] Heat treatment includes optional heat treatment pretreatment and actual calcination.
[0020] Choosing the pressure during the compression period in option c) results in a preferred density of 1.72 g / cm³ for the precursor molded body. 3 Up to 2.28 g / cm 3 The preferred value is 1.74 g / cm³. 3 Up to 2.26 g / cm 3 The preferred value is 1.76 g / cm³.3 Up to 2.24 g / cm 3 The optimal value is 1.78 g / cm³. 3 Up to 2.22 g / cm 3 The optimal value is 1.80 g / cm³. 3 Up to 2.20 g / cm 3 .
[0021] d) The weight loss during heat treatment is preferably 26 to 39 wt%, more preferably 27 to 38 wt%, particularly preferably 28 to 37 wt%, very particularly preferably 29 to 36 wt%, and most preferably 30 to 35 wt%.
[0022] Weight loss during heat treatment can be adjusted, for example, by using substances that decompose during the heat treatment process.
[0023] Suitable cylindrical structures are cylindrical bodies with a central circular continuous opening in the longitudinal direction (hollow cylinder) and three-fold concave cylindrical bodies with three circular continuous openings evenly arranged in the longitudinal direction. The latter cylindrical structure is described in WO 2021 / 239483.
[0024] The shortest distance between the outer wall of the cylindrical body and the next consecutive opening is preferably 0.75 mm to 2.5 mm, more preferably 0.8 mm to 2.0 mm, particularly preferably 1.0 mm to 1.8 mm, very particularly preferably 1.2 mm to 1.7 mm, and most preferably 1.3 mm to 1.6 mm. In the case of a hollow cylinder, the shortest distance between the outer wall of the cylinder and the next consecutive opening corresponds to the wall thickness of the hollow cylinder.
[0025] The molybdenum content of the solid catalyst molded body, calculated as MoO3, is preferably from 45% to 75% by weight, particularly preferably from 50% to 70% by weight, and very particularly preferably from 55% to 65% by weight.
[0026] The bismuth content of the solid catalyst molded body, calculated as Bi2O3, is from 1 wt% to 20 wt%, particularly preferably from 2 wt% to 15 wt%, and very particularly preferably from 3 wt% to 10 wt%.
[0027] The iron content of the solid catalyst molded body, calculated as Fe2O3, is 2 to 12 wt%, particularly preferably 3 to 11 wt%, and very particularly preferably 4 to 10 wt%.
[0028] The cobalt and nickel content of the solid catalyst molded body, calculated as CoO and NiO, is from 9 to 30 wt%, particularly preferably from 12 to 27 wt%, and very particularly preferably from 15 to 24 wt%.
[0029] Solid catalyst molds may also contain elements potassium and / or silicon.
[0030] This invention also relates to a solid catalyst molded body with a cylindrical structure prepared according to the method of the invention for the gas-phase oxidation of olefins and / or alcohols to α,β-unsaturated aldehydes and / or α,β-unsaturated carboxylic acids, wherein the solid catalyst molded body contains at least the elements molybdenum, bismuth, iron, and cobalt, and is characterized in that the density of the solid catalyst molded body is 1.20 g / cm³. 3 Up to 1.70 g / cm 3 The density of the solid catalyst molded body is the quotient of its mass and geometric volume, and the total pore volume of the solid catalyst molded body is 0.33 cm³. 3 / g to 0.60cm 3 / g, and the pore volume of the solid catalyst molded body in the range of 0.1μm to 1μm is 85% to 99% of the total pore volume, wherein the total pore volume and the pore volume in the range of 0.1μm to 1μm are determined by mercury porosity determination method.
[0031] Geometric volume is the macroscopic volume of a solid catalyst mold, including pores. For completeness, it should be emphasized that continuous, substantially circular pores and any surface structures such as grooves, notches, or serrations are not part of the macroscopic volume.
[0032] The density of the solid catalyst molded body is preferably 1.22 g / cm³. 3 Up to 1.68 g / cm 3 The preferred value is 1.24 g / cm³. 3 Up to 1.66 g / cm 3 The preferred value is 1.26 g / cm³. 3 Up to 1.64 g / cm 3 The preferred value is 1.28 g / cm³. 3 Up to 1.62 g / cm 3 The optimal value is 1.30 g / cm³. 3 Up to 1.60 g / cm 3 .
[0033] The total pore volume of the solid catalyst molded body is preferably 0.34 cm³. 3 / g to 0.58cm 3 / g, preferably 0.35cm 3 / g to 0.56cm 3 / g, particularly preferably 0.36cm 3 / g to 0.54cm 3 / g, with a very special preference of 0.37cm 3 / g to 0.52cm 3 / g, the optimal value is 0.38cm 3 / g to 0.50cm 3 / g.
[0034] The pore volume of the solid catalyst molded body in the range of 0.1 μm to 1 μm is preferably 86% to 98% of the total pore volume, more preferably 87% to 97%, particularly preferably 88% to 96%, and very particularly preferably 89% to 95%.
[0035] The preferred solid catalyst mold is a multi-component oxide of general formula I.
[0036] Mo 12 Bi a Fe b Co c Ni d X e Y f Z g O n (I)
[0037] in,
[0038] X = K, Cs and / or Rb
[0039] Y=Ca,Sr,Ba,Li,Na,Cr,W,Mn,Cu,Zn,Ga,P,B,As,Sn,Sb,Te,Nb,Ta,Pb,Ce and / or La
[0040] Z = Si, Al, Ti, Zr and / or Mg
[0041] a = 0.2 to 2
[0042] b = 1 to 4
[0043] c = 3 to 9
[0044] d = 0 to 4
[0045] c+d = 4 to 9.5
[0046] e = 0.01 to 0.5
[0047] f = 0 to 10
[0048] g = 0 to 10
[0049] n = a number determined by the valence and abundance of the elements other than oxygen in general formula I.
[0050] The present invention also relates to a method for preparing α,β-unsaturated aldehydes and / or α,β-unsaturated carboxylic acids, wherein olefins and / or alcohols, particularly propylene, are passed together with molecular oxygen through a fixed-bed reactor comprising a solid catalyst molded body bed according to the present invention and a fixed-bed reactor comprising a solid catalyst molded body bed according to the present invention.
[0051] This invention is based on the understanding that the pressure applied during the preparation of the precursor mold and the weight loss that occurs during heat treatment have a significant impact on the selectivity and yield of the valuable product.
[0052] The preparation of solid catalyst molds is described below:
[0053] The solid catalyst molded bodies obtainable according to the present invention are generally molded essentially into geometrically molded bodies, calcined, and used for catalytic partial oxidation of corresponding heterogeneous gases (particularly partial oxidation of propylene to acrolein). Essentially, the desired geometry of the solid catalyst is not limited.
[0054] In principle, solid catalyst molds can be prepared in a simple manner by preparing a tightly packed, preferably finely separated dry mixture from a suitable source of its elemental composition (particularly a source other than oxygen), the composition of which corresponds to the stoichiometry of the solid catalyst mold to be prepared, and calcining the dry mixture at a temperature of 350°C to 650°C after prior molding to form a precursor mold, optionally using molding aids. Calcination can be carried out under an inert gas and oxidizing atmosphere, such as air (or another mixture of an inert gas and molecular oxygen, which may also contain a relatively low proportion of reducing active components), or under a reducing atmosphere (e.g., a mixture of inert gases, NH3, CO, and / or H2, which may also contain a relatively low proportion of oxidizing active components) or under vacuum. Calcination times can range from a few minutes to several days, generally decreasing with increasing calcination temperature.
[0055] Suitable sources of elemental composition for a solid catalyst mold (i.e., starting compounds containing at least one chemically bonded elemental component (at least one element contained in the solid catalyst mold)) are compounds that are already oxides (typically existing in a solid aggregate state under normal conditions (1 atm, 0 °C)) (e.g., metal oxides) and / or compounds that have been converted to oxides (typically existing in a solid aggregate state under normal conditions) by heating (heat treatment at high temperatures), at least in the presence of components that release gaseous oxygen and / or gaseous (e.g., molecular) oxygen. In principle, the oxygen source can be a component of the mixture to be calcined, for example, in the form of peroxides. Typically, the starting compound can be a source of several elemental components for the solid catalyst mold.
[0056] In addition to oxides, suitable starting compounds (sources) are particularly halides, nitrates, formates, acetates, oxalates, citrates, carbonates, amine complexes, ammonium salts and / or hydroxides, as well as hydrates of the above salts.
[0057] Compounds such as NH4OH, (NH4)2CO3, NH4NO3, NH4CHO2, CH3COOH, NH4CH3CO2, and / or ammonium oxalate, which decompose substantially completely and / or decompose into gaseous compounds (e.g., ammonia, CO2, CO, H2O, nitrogen oxides) during subsequent calcination, can be additionally incorporated into a tightly packed dry mixture. Such substances decomposed during calcination are also organic materials, such as stearic acid, malonic acid, ammonium salts of the above acids, starches (e.g., potato starch, corn starch), ground nut shells, and finely separated plastic powders (e.g., polyethylene, polypropylene, etc.).
[0058] When the elemental source portion used to produce a dry mixture that is as close as possible and preferably finely separated is organic (e.g., in the case of acetate, formate, oxalate and / or citrate) or contains hydroxide ions, carbonate ions, bicarbonate ions, ammonium ions, halide ions, hydrogen phosphate ions and / or nitrate ions that typically decompose during calcination, gaseous compounds are usually formed (released) within the scope of the heat treatment.
[0059] The close mixing of the starting compound (source) used to prepare the solid catalyst mold can be carried out in either dry or wet form. If carried out in dry form, the starting compound (source) is advantageously used as a finely separated powder and calcined after mixing and compaction to form the geometric precursor mold.
[0060] However, according to the present invention, the close mixing of the (elemental) sources is preferably carried out in a wet form.
[0061] In this case, the starting compounds are mixed together in the form of solutions and / or suspensions, and the resulting wet (preferably aqueous) mixture M is then dried to form a compact dry mixture. The solvent and / or suspending agent preferably used is water or an aqueous solution, and the resulting wet mixture M is an aqueous mixture M.
[0062] In the above mixing process, if the mixture is started only from a source existing in dissolved form and / or from a colloidal dissolved source of the elemental component, a very particularly dense dry mixture is obtained. As previously mentioned, the starting compound can be a source of only one or more elemental components. Correspondingly, the above solution or colloidal solution can contain only one or more elemental components of the relevant solid catalyst mold to be prepared. As previously mentioned, the preferred solvent is water. The drying of the resulting aqueous mixture is preferably carried out by spray drying.
[0063] When referring to a solution of a source (starting compound, starting substance) in a solvent (especially water) in this literature, the term "dissolution" means a molecular or ionic solution. That is, the largest geometric unit of the starting substance (source) dissolved in the solution must have a "molecular" size, and the solution appears "optically empty".
[0064] In contrast, colloidal solutions represent a link between real (molecular and / or ionic) solutions and suspensions. In these colloidal dispersions, there exists a small accumulation of molecules or atoms, invisible to the naked eye or microscope. Colloidal solutions appear optically completely transparent (although often colored) because the particles they contain have diameters ranging from 1 nm to 250 nm (preferably up to 150 nm, particularly preferably up to 100 nm).
[0065] Due to their small size, colloidally dissolved particles cannot be separated by conventional filtration. However, they can be separated from their "solvent" by ultrafiltration using membranes of plant, animal, or artificial sources (such as parchment, pig bladder, or cellophane). Unlike real (molecular and / or ionic) solutions that are "optically empty," a beam of light cannot pass through a colloidal solution without deflection. The beam is scattered and deflected by the colloidally dissolved particles. To maintain the stability of colloidal solutions and prevent further particle aggregation, they typically contain wetting agents and dispersants, as well as other additives.
[0066] To prepare a wet (preferably aqueous) mixture M, it is preferable to introduce elements other than silicon into the solid catalyst molded body in the form of a solution (particularly preferably in an aqueous solution), and preferably to introduce silicon in the form of a silica sol to prepare the wet (preferably aqueous) mixture M.
[0067] Silica sol is a colloidal solution of nearly spherical polysilicic acid particles. The particle diameter is within the colloidal range, between 5 nm and 75 nm depending on the type. The particles are non-porous. They have a surface-hydroxylated SiO2 core. Individual spherical particles are not cross-linked to each other. For stability reasons, some hydroxyl groups are usually present in silica sol in the form of neutralization with alkali metal hydroxides and / or ammonium hydroxide. This means that the counterion is not a proton in some cases, but an alkali metal ion (e.g., Na+). + ) and / or NH4 + Cationic. The SiO2 content of silica sol suitable for preparing wet (preferably aqueous) mixtures M can be, for example, 30% to 60% by weight of the silica sol. Silica sol is typically aqueous and contains no precipitable components. It can usually be stored for many years without precipitation.
[0068] A particularly suitable silicon source is silica sol from Grace GmbH & KG. Address: Hollerecke 1, D-67545 Worms. Its particles are discrete, homogeneous silica spheres with no internal surface or detectable crystallinity. The majority of its composition is dispersed in an alkaline medium, which reacts with the hydroxylated surfaces and generates a repulsive negative charge.
[0069] Suitable silica sols can have very narrow (basically monodisperse) or very wide (polydisperse) particle sizes.
[0070] The silica sol particularly suitable for the purposes of this invention (for the preparation of wet (preferably aqueous) mixtures M) is silica sol LUDOX TM50 from Grace Corporation. Silica sol LUDOX TM50 has a substantially monodisperse (d = 22 nm) particle size distribution. Its pH value (1 atm, 25°C) is 9.0. The alkali metal ion that substituted part of the hydroxyl protons is Na. + The SiO2 content of LUDOX™ 50 is 50% of the weight of the hydrogel. The specific surface area of the SiO2 particles contained in the LUDOX™ 50 colloidal solution is 140 m². 2 The bulk density (1 atm, 25°C) of LUDOX TM50 is 1.40 g / cm³. 3 The titratable alkali content (calculated as Na2O) of LUDOX TM50 is 0.21% by weight (based on the weight of silica sol).
[0071] The dynamic viscosity of LUDOX TM50 is 40 mPas (1 atm, 25°C). The Cl of LUDOX TM50... - The content (calculated as NaCl) of SO4 in LUDOX TM50 is 0.03% by weight. 2- The content (calculated as Na2SO4) is 0.08% by weight (based on the weight of LUDOX TM50 in each case).
[0072] Of course, in the solution used to prepare a wet (especially aqueous) mixture M, at least one elemental source dissolved in molecules and / or ions, as well as one or more other elemental sources dissolved in colloids, may also be present side by side.
[0073] A favorable source of molybdenum is ammonium heptamolybdate tetrahydrate. This is primarily due to its excellent solubility in water. According to Ullmann's Encyclopedia of Industrial Chemistry, Vol. 22, 2003, WILEY-VCH, pp. 320 / 321, ammonium molybdate tetrahydrate has a saturated solubility of 30% by weight in an aqueous solution at 25°C and 1 atm (calculated as anhydrous salt).
[0074] During the preparation process, ammonium molybdate tetrahydrate may be contaminated by small amounts (typically ppm) of isopolymolybdates insoluble in water (due to a lack of strict adherence to process parameters). If ammonium heptamolybdate tetrahydrate contaminated in this manner dissolves in water, an aqueous solution is formed, which exhibits turbidity due to the small amount of undissolved, finely separated isopolymolybdates. The applicant's own research indicates that even ammonium molybdate tetrahydrate contaminated with isopolymolybdates, when its aqueous solution (as measured as described in WO 2016 / 147324) has a turbidity of 20 NTU, or 50 NTU, or 70 NTU, or 100 NTU, or 150 NTU, or 200 NTU, or 250 NTU, is suitable for preparing solid catalyst molds according to the invention, and its performance is not significantly impaired when used as a catalyst for the heterogeneous partial gas-phase oxidation of propylene as the main product and acrolein as a byproduct.
[0075] Other suitable molybdenum sources include, for example, ammonium orthomolybdate ((NH4)2MoO4), ammonium dimolybdate ((NH4)2Mo2O7), and ammonium tetramolybdate dihydrate ((NH4)2Mo4O7). 13 x 2H2O) and ammonium decamolybdate dihydrate ((NH4)4Mo 10 O 32 (x 2H2O). However, molybdenum trioxide can also be used in principle.
[0076] In the context of preparing solid catalyst molds, the preferred source of alkali metals is their hydroxides. However, in principle, nitrates of these elements and hydrates of these nitrates can also be used as such sources. That is, the preferred K source is KOH, but in principle, KNO3 or its hydrate can also be used as a K source.
[0077] The preferred Bi source is a bismuth salt, where Bi is Bi2. 3+ Suitable salts are, for example, bismuth(III) oxide, bismuth(III) nitrate oxide (bismuth subnitrate), and bismuth(III) halides (e.g., fluorides, chlorides, bromides, iodides), especially bismuth(III) nitrate pentahydrate. Of course, solutions of elemental Bi in aqueous nitric acid can also be used as Bi sources, where Bi is in the form of Bi... 3+ It exists in the form of Bi. 3+ When an aqueous solution of nitrate or its hydrate is used as the source (preferred according to the invention) (such a solution can also be produced by dissolving elemental Bi in an aqueous nitric acid solution), according to the invention, a low pH (1 atm, 25°C) is advantageous because it counteracts the undesirable Bi content in the aqueous solution. 3+Precipitation formation. The pH value is preferably ≤1, more preferably ≤0.5. However, typically the pH value is ≥-2, and usually ≥0. This aqueous solution is advantageously nitric acid. That is, its low pH value is caused by excess nitric acid (in this case, the aqueous solution contains NO3). - (n NO3- The molar amount and the Bi3 content in the aqueous solution + (n Bi3+ The molar ratio of molar quantities (n) NO3- ) / (n Bi3+ )>3).
[0078] The preferred Fe source is Fe 3+ Salts, of which various ferric(III) nitrate hydrates are particularly preferred (see, for example, DE 102007 003076A1). According to the invention, ferric(III) nitrate nonahydrate is particularly preferred as the Fe source for the aforementioned purpose. Of course, Fe... 2+ Salts can also be used as a source of Fe.
[0079] To prepare a solid catalyst mold, at least 50 mol% of Fe source form, more preferably at least 75 mol% and most preferably at least 95 mol% or 100 mol% of Fe is advantageously introduced, based on the total molar amount of Fe contained therein, which has the properties of Fe as Fe source form. 3+ Fe. Also contains Fe. 3+ and Fe 3+ The Fe source can also be used for this purpose.
[0080] A particularly suitable source of Co is its salt, which is used in the form of Co. 2+ and / or Co 3+ The form of the source contains Co. Examples that can be mentioned are cobalt(II) nitrate hexahydrate, Co3O4, CoO, cobalt(II) formate, and cobalt(III) nitrate. For the purposes described above, the former of these sources is particularly preferred. Of course, a solution of elemental Co in an aqueous nitric acid solution can also be used as a Co source, wherein Co is in the form of Co... 2+ It exists in the form of.
[0081] Given the elemental composition Ni, Ni is preferred. 2+ Salts. These are in particular nickel(II) carbonate, nickel(II) sulfate, nickel(II) oxide, nickel(II) acetate, nickel(II) formate, nickel(II) hydroxide, nickel(II) oxalate, and nickel(II) nitrate, and their corresponding hydrates. Hydrates of nickel(II) nitrate (e.g., its hexahydrate) are particularly preferred as Ni sources.
[0082] To improve the solubility of salts such as Fe, Co and / or Ni in aqueous media, ammonia (also as their aqueous solution) and / or nitric acid (especially as their aqueous solution) may be added to the corresponding solution as needed.
[0083] Basically, the preparation of a wet (e.g., aqueous) mixture M can be carried out in various gaseous atmospheres (e.g., air, argon, nitrogen, water vapor, and / or carbon dioxide). According to the invention, the preparation of the wet (e.g., aqueous) mixture M is preferably carried out in air (the aqueous mixture M is advantageously saturated in air). When Co 2+ Salt and Fe 2+ This is especially true when salts are used as sources of cobalt and iron, particularly when these salts are nitrates and / or their hydrates.
[0084] As previously stated, according to the present invention, the wet mixture M is preferably an aqueous mixture M, which is particularly advantageously prepared in the following manner.
[0085] An aqueous solution A with a pH value ≤3, preferably ≤2, particularly preferably ≤1, and very particularly preferably ≤0 is prepared from at least one element Fe source, at least one element Bi source, at least one element Co source, and optionally at least one element Ni source. (In this specification, the pH value of the aqueous solution generally (unless otherwise explicitly stated) refers to a measurement performed at 1 atm and the temperature at which the corresponding aqueous solution was prepared using a glass electrode designed as a single-bar measuring chain; the calibration of the single-bar measuring chain required in this regard is performed under the same conditions using an aqueous buffer solution whose pH value is known under these conditions and close to the desired measurement value; the Mettler Toledo pH electrode Inpro 4260 / 425 / Pt 100 is particularly suitable for determining such pH values, as it is a single-bar measuring chain with an integrated temperature sensor Pt 100 for automatic temperature compensation.) Typically, the pH value of aqueous solution A is not less than -2, and particularly advantageously in the range of -1 to 0. Aqueous solution A is preferably an aqueous solution of the nitrate or nitrate hydrate of the above-mentioned elements. Aqueous solution A is particularly preferred to be an aqueous solution of these nitrates or nitrate hydrates in an aqueous nitric acid solution. Solutions of related elements in an aqueous nitric acid solution are also particularly suitable as element sources for preparing this solution.
[0086] Aqueous solution B is prepared from at least one elemental Mo source and optionally at least one alkali metal source. The pH of aqueous solution B is advantageously <7 (at 1 atm and the temperature at which solution B is prepared). The pH of aqueous solution B is particularly preferably ≤6.5, and very particularly advantageously ≤6. Typically, the pH of aqueous solution B is ≥3. The advantageous pH of solution B used according to the invention is 4 to 6. According to the invention, an elemental hydroxide of an alkali metal (e.g., KOH) is preferably used as the alkali metal source for preparing aqueous solution B. The preferred Mo source for preparing aqueous solution B is ammonium heptamolybdate tetrahydrate ((NH4)6Mo7O). 24 x4H2O) is completely soluble in water at 25°C (1 atm) to saturation solubility (30% by weight, calculated anhydrous).
[0087] According to the present invention, based on the total amount of aqueous solution A, the total content of metal components such as Bi, Fe, Co, Ni, etc. in aqueous solution A is advantageously from 5% to 20% by weight, and advantageously from 10% to 15% by weight.
[0088] According to the invention, based on the total amount of aqueous solution B, the total Mo content of aqueous solution B is advantageously from 2% to 25% by weight, advantageously from 3% to 20% by weight, and particularly advantageously from 5% to 15% by weight.
[0089] Then, aqueous solution A and aqueous solution B are advantageously mixed together. Advantageously, aqueous solution A is continuously stirred into aqueous solution B. Advantageously, the initially introduced aqueous solution B is vigorously stirred.
[0090] According to the present invention, based on the total amount of the aqueous mixture, the total content of metal components such as Bi, Fe, Co, Ni, Mo, etc. in the resulting aqueous mixture of aqueous solution A and aqueous solution B is advantageously from 3% to 20% by weight, and advantageously from 5% to 15% by weight.
[0091] The temperature of the initially introduced aqueous solution B, the temperature during stirring of the aqueous solution A, and the temperature of the aqueous solution A itself are advantageously (preferably throughout the mixing process) ≤80°C and ≥0°C. These temperatures are preferably ≤75°C and ≥30°C, particularly preferably ≤70°C and ≥50°C or ≤65°C and ≥55°C.
[0092] Advantageously, aqueous solutions A and B, as well as the aqueous mixture produced when aqueous solution A is stirred into aqueous solution B, have the same temperature. Preferably, it is 60°C. More preferably, the temperatures of aqueous solutions A, B, and the resulting aqueous mixture are kept constant during the stirring process. This can be achieved, for example, by means of a water bath. When aqueous solution A is stirred into aqueous solution B, the working pressure is advantageously 1 atm (1.01 bar).
[0093] The aqueous solution A is preferably stirred into the initially introduced aqueous solution B within a time range of 5 to 60 minutes, particularly preferably within 10 to 30 minutes, and very particularly preferably within 15 to 25 minutes. The resulting aqueous mixture is then conveniently stirred for 5 to 60 minutes, preferably 10 to 30 minutes, particularly advantageously 15 to 25 minutes, while preferably maintaining the stirring temperature.
[0094] The pH of the aqueous mixture of aqueous solution A and aqueous solution B is preferably ≤3, more preferably ≤2. Typically, its value is ≥0.
[0095] If the solid catalyst molding contains the elemental component Si, according to the invention, it is preferable to use an aqueous silica sol as its source and stir it into an aqueous mixture of aqueous solution A and aqueous solution B. Water can be advantageously added to this aqueous mixture before stirring. The aqueous silica sol and water can be conveniently added at once. In this case, the temperature of both the water and the aqueous silica sol advantageously corresponds to the temperature of the aqueous mixture of aqueous solution A and aqueous solution B. Finally, it is conveniently stirred for up to 30 minutes. During subsequent stirring, the aforementioned temperature is advantageously maintained. The SiO2 content of the added aqueous silica sol can be 15% to 60% by weight, or 20% to 60% by weight, or 30% to 60% by weight, preferably 40% to 60% by weight, and particularly preferably 45% to 55% by weight (in each case based on its total weight).
[0096] Instead of initially introducing aqueous solution B into the thermostatically stirred vessel, and then introducing aqueous solution A while stirring, aqueous solutions B and A can also be continuously supplied to the stirred vessel (e.g., via a "3-way T-type mixer"). In principle, aqueous solution B can also be continuously stirred into the initially introduced aqueous solution A. However, this method is less preferred.
[0097] Typically, the available aqueous mixture M is an aqueous suspension (preferably, the aqueous mixture M also has the aforementioned advantageous ratio V (containing NH3 + NH4)). +The total molar amount of the aqueous mixture M and the molar amount of Mo contained therein; furthermore, the pH of the available aqueous mixture M is advantageously ≤3, typically 0 to 2. The available aqueous mixture M advantageously contains no more than or less than 60 molar percentages of the total molar amount of Co and / or Ni dissolved in the aqueous medium (at the temperature and operating pressure at which the aqueous mixture M is produced). The above-mentioned content dissolved in the aqueous medium of the aqueous mixture M is preferably ≤50 molar percentages relative to the total molar amount of Co and / or Ni contained in the aqueous mixture M, particularly preferably ≤40 molar percentages, or ≤30 molar percentages or ≤20 molar percentages. According to the invention, based on the amount of the aqueous mixture M, the total content of Bi, Fe, Mo, etc. in the aqueous mixture M to be dried (preferably spray dried) is conveniently from 3 wt% to 20 wt%, advantageously from 5 wt% to 15 wt%. Typically, AT ≥ 10 wt% or ≤ 15 wt%.
[0098] According to the invention, the aqueous mixture M is preferably converted into a finely separated, tightly packed dry mixture by spray drying (the drying of the aqueous mixture M is preferably carried out as quickly as possible before its preparation). That is, the aqueous mixture M is first separated (sprayed) into finely separated droplets in a spray dryer, and then dried in the spray dryer. Spray drying is preferably carried out in a hot gas stream. However, in principle, other hot gases (e.g., nitrogen or air diluted with nitrogen and other inert gases) can also be used for the above-described spray drying.
[0099] Spray drying can be carried out in a co-current or counter-current manner with respect to hot gas. Typical gas inlet temperatures range from 250°C to 450°C, preferably from 270°C to 370°C, and typical gas outlet temperatures range from 100°C to 160°C. Spray drying is preferably carried out simultaneously with the hot gas.
[0100] The resulting spray powder typically has an average particle size of 10 μm to 100 μm, preferably 15 μm to 60 μm, and particularly preferably 25 μm to 50 μm (the diameter is determined by light scattering of the spray powder dispersed in air (dispersion pressure 1.0 bar) according to ISO 13320-1). Generally, references to standards in this document refer to the standard version that was valid as of the priority date of this patent application, and whose publication date has the smallest time difference from the priority date of this patent application.
[0101] The vibration bulk density (25°C, 1 atm) of the sprayed powder is typically from 500 g / l to 1300 g / l, preferably from 700 g / l to 1100 g / l.
[0102] The annealing loss of sprayed powder (after static annealing in excess air at 600°C (powder temperature) for 3 hours) is typically 20% to 40% of its starting weight, preferably 25% to 35% of its starting weight.
[0103] Prior to further processing, the spray powder can preferably be stored in an airtight container (e.g., a plastic drum). The storage temperature should not exceed 70°C, and preferably ≤50°C. The storage temperature should generally not fall below 10°C. Since spray powder is typically hygroscopic, prolonged contact with humid air should be avoided. Contact with humid air will impair the processability of the spray powder (e.g., its flowability) and ultimately reduce the catalytic activity of the solid catalyst molded bodies prepared from it.
[0104] Of course, the aqueous mixture M can also be dried by other drying methods, such as conventional evaporation (preferably under reduced pressure; the drying temperature is usually no more than 150°C). In principle, the aqueous mixture M can also be dried by freeze-drying or... It is done by drying.
[0105] The sprayed powder can be coarsened first, for example, by subsequent compaction. If the compaction is dry, finely separated graphite and / or other molding aids (e.g., lubricants, reinforcing agents, and / or pore-forming agents) mentioned in this document can be mixed into the sprayed powder prior to compaction (e.g., using a spiral mixer). For example, compaction can be performed using a calender with two steel rollers in opposite directions. Subsequently, the compacted material can be directionally crushed to a particle size suitable for further use. This can be achieved in the simplest way, for example, by pressing the compacted material through a sieve with a defined mesh size.
[0106] However, compaction can also be carried out under moist conditions. For example, spray powders can be kneaded by adding water. After kneading, the kneaded composition can be further pulverized to the desired fineness for subsequent use (see, for example, DE100 49 873A1) and dried.
[0107] Solid catalyst molds are prepared by pressing (compressing or compacting) precursor molds with regular or irregular geometries and then heat-treating them. These molds are formed from finely separated precursor compositions (fine, compact, dry mixtures of elemental composition sources).
[0108] As molding aids for further fine separation, such as lubricants like graphite, carbon black, polyethylene glycol, polyacrylic acid, stearic acid, starch, mineral oil, vegetable oil, water, boron trifluoride, and / or boron nitride, can be added again to the precursor composition for fine separation. Furthermore, suitable molding aids are reinforcing agents, such as microfibers of glass, asbestos, silicon carbide, or potassium titanate, which have a beneficial effect on the cohesiveness of the resulting compact (the molded body) after molding is completed by compression. Pore-forming agents such as ammonium nitrate, ammonium carbonate, water, and / or malonic acid are also suitable as molding aids. During heat treatment, the pore-forming agent decomposes or evaporates, forming pores. For example, the common use of lubricants in the respective molding processes is described in documents DE 10 2007 004961A1, WO 2008 / 087116, WO 2005 / 030393, US2005 / 0131253, WO 2007 / 017431, DE 10 2007 005606A1 and DE 10 2008 040093A1.
[0109] Preferably, only fine-grained graphite is used as a lubricant. In this case, the fine-grained graphite that can be used is particularly those recommended in WO 2005 / 030393, US2005 / 0131253, WO 2008 / 087116, and DE 10 2007 005606A1. This is especially true for the graphite used in the examples and comparative examples in these documents. Very particularly preferred graphite is from Asbury Graphite Mills, Inc., New Jersey 08802, USA (Asbury 3160 and Asbury 4012), and from Timcal Ltd., 6743 Bodio, Switzerland. T44.
[0110] Based on the weight of the fine-particle precursor composition to be molded, and based on its total weight, the fine-particle precursor composition may contain, for example, up to 15% by weight of a fine-particle lubricant (e.g., graphite). However, in most cases, the lubricant content in the finely separated precursor composition to be molded (in a finely separated, tightly dry mixture) is ≤9% by weight, in many cases ≤5% by weight, and in many cases ≤4% by weight; this is especially true when the finely separated lubricant is graphite. Typically, the above-mentioned addition amount is ≥0.5% by weight, and usually ≥2.5% by weight.
[0111] Typically, a finely separated precursor composition (a finely separated, tightly packed dry mixture) optionally containing molding aids is compressed into the desired geometry of the precursor molded body by applying external force (pressure) to the precursor composition. There are no limitations on the molding equipment or molding method used in this case.
[0112] For example, compression molding can be achieved by tableting. In this case, contact drying is preferably performed using a finely separated precursor composition (a finely separated, tightly packed dry mixture). However, it may contain, for example, up to 10% by weight of additives that are liquid under normal conditions (25°C, 1 atm (1.01 bar)). The finely separated precursor composition (a finely separated, tightly packed dry mixture) may also contain solid solvates (e.g., hydrates) that comprise such liquid substances in chemically and / or physically bound forms. Of course, the finely separated precursor composition may also be completely free of these substances.
[0113] The preferred molding method for the finely separated precursor composition (a finely separated, tightly packed dry mixture) by compression is tableting. The basic principles of tableting are described, for example, in "Die Tablette," a manual for development, preparation, and quality assurance, WARitschel and A. Bauer-Brandl, 2nd edition, Edition Verlag Aulendorf, 2002, and can be directly transferred to the tableting method according to the invention.
[0114] Tableting is a process of suppressing agglomerates. A free-flowing feed mixture is introduced into a pressing tool with a die between two punches, and compressed by uniaxial compression to form a solid tablet. Tableting can be divided into four parts: metering inlet, compression (elastic deformation), plastic deformation, and discharge. Tableting is performed, for example, on a rotary press or an eccentric press.
[0115] The outer surface of the tableting catalyst carrier consists of a circumferential surface corresponding to the inner wall of the mold cavity and a first end face and a second side face corresponding to the operating head of the punch. The tableting catalyst carrier can be flat or have curved ends, i.e., at least one of the first and second side faces is curved. For example, curved sides can be obtained by using a concave lower punch and / or an upper punch. If desired, the upper punch and / or lower punch may include protruding pins to form internal channels. Multiple pins can also be provided for the pressing punch, such that, for example, a punch with four pins can be prepared to prepare a molded body with four holes (channels). Typical design features of such pressing tools can be found, for example, in US 8,865,614.
[0116] Pressing tools typically consist of a die, an upper punch, a lower punch, and a pin (if the die body has a channel). Suitable materials for pressing tools are tool steel, tungsten carbide (WC)-based cemented carbide, and ceramic materials. Preferred tool materials have a Rockwell C hardness greater than 55. Examples of tool steel materials are DIN tool steels 1.2210, 1.2343, 1.2436, 1.2379, 1.2601, 1.2080, 1.25550 and high-speed steels, Vanadis 4 Extra from Uddeholm D-40549 Düsseldorf, and Vanadis 8 from Uddeholm D-40549 Düsseldorf. Suitable WC-based materials are described in US 8,865,614. An example of such WC-based materials is from a company located at D70497 Stuttgart. G10-Ni and of An example of a ceramic material is yttrium-stabilized zirconia (YSZ).
[0117] WC-based cemented carbide and ceramic materials are particularly suitable for tool inserts in which lined molds made of WC-based cemented carbide or ceramic are inserted into steel housings made of tool steel (e.g., 1.2379).
[0118] Pressing tools typically have surface coatings to improve surface hardness, corrosion resistance, wear resistance, abrasion resistance, and non-adhesion. Examples of surface coating types are diamond, such as carbon (DLC), boron nitride, titanium nitride, chromium nitride, plasma-plated chromium, and hard chromium. The layer thickness ranges from 1 μm to 10 μm, preferably from 1 μm to 5 μm.
[0119] The surface of the compression tool that comes into contact with the feed mixture and the resulting tablets preferably has a low surface roughness. According to DIN 4768, the arithmetic mean roughness value Ra of the compression tool surface is preferably 0.01 μm to 0.5 μm, particularly preferably 0.02 μm to 0.3 μm, even more preferably 0.02 μm to 0.2 μm, and very particularly preferably 0.02 μm to 0.1 μm.
[0120] The length of the straight tip of the lower punch is preferably 2 mm to 7 mm, particularly preferably 2 mm to 6 mm, and very particularly preferably 2.5 mm to 5 mm. Excessive tip straightness can lead to high friction, especially when adhesion of the precursor molded body occurs. Preferably, the upper and lower edges of the lower punch tip are not rounded, but sharp. Sharp edges reduce powder clogging at the punch-hole interface and pinhole interface (for tablet molds with channels). Powder clogging can lead to powder adhesion and leakage.
[0121] The tip length of the upper punch is preferably greater than 2 mm, and is typically in the range of 2 mm to 10 mm. Unlike the lower punch, the high tip length does not cause friction problems because the upper punch only inserts a few millimeters into the die during the tableting cycle.
[0122] If the tablet mold has a channel, the lower punch and upper punch have holes for receiving pins. The upper punch should have at least one vent hole to allow air to escape from the mold cavity to the outside of the upper punch hole during the pressing process. Such an upper punch with a vent hole is disclosed in US2010 / 0010238 (see Figures 4a, 4b, 4c and 4d).
[0123] The distance between the nozzle orifice and the outer surface of the lower punch is preferably 3 μm to 50 μm, particularly preferably 5 μm to 35 μm, and very particularly preferably 6 μm to 26 μm. Similarly, the distance between the die orifice and the outer surface of the upper punch is preferably 3 μm to 50 μm, particularly preferably 5 μm to 35 μm, and very particularly preferably 6 μm to 26 μm. The distance is ensured by selecting an appropriate combination of dimensional tolerances for the die and the lower punch. Dimensional tolerances are typically expressed according to ISO shaft tolerances as defined in ISO 286-2. Examples of dimensional tolerance combinations for the nozzle orifice and the outer surface of the punch shown in ISO tolerance codes are H6 / f7, H6 / g6, H6 / g7, H7 / g6, H7 / f7, F8 / h6, G7 / h6, and F7 / h6 (nozzle orifice / outer surface of lower punch).
[0124] When the tablet mold has a channel, the pressing tool includes a pin. The distance between the pin hole of the lower punch and the pin is preferably 3 μm to 50 μm, particularly preferably 5 μm to 35 μm, and very particularly preferably 6 μm to 26 μm. Similar to the distance between the mold hole and the outside of the punch, this distance is ensured by selecting an appropriate combination of the dimensional tolerances of the mold and the lower punch.
[0125] The die orifice preferably has a slight taper starting from a defined depth in the direction of the die top. The tapered portion of the nozzle orifice has a gradually increasing orifice size in the direction of the nozzle top, thus creating an additional distance between the nozzle orifice wall and the straight outer surface of the lower punch tip. This additional space helps to expel air contained in the mixed feed during compression in the die, thereby reducing powder blow-off and unstable tableting due to poor air expulsion. Another advantage of the tapered die is easier ejection after compression. Due to the embossing through the tapered die orifice, compression into tablets at the tapered location of the die orifice produces tablets with a slightly tapered outer surface. During the ejection phase, where the lower punch pushes the tablet upwards in the die, the tablet is easily ejected from the die wall because the slight lifting of the tablet due to the tapered structure forces the tablet to separate from the die wall. When the die orifice is not tapered, the tablet does not separate from the die wall, and therefore the entire ejection process (i.e., the tablet is pushed upwards from the depth where compression occurs to the nozzle top) is subject to friction between the outer surface of the tablet and the die wall, and between the straight outer surface of the tip and the nozzle wall. This friction results in an unfavorable ejection force.
[0126] The depth of the die taper (i.e., the depth from the top of the die) should be selected so that the formed tablet is primarily located in the tapered region before ejection. To achieve this, the depth of the die taper can be oriented by adding the height of the tablet within the die before elastic recovery (i.e., the minimum distance between the upper and lower punches) and the insertion depth of the upper punch. For example, a taper depth of 12mm to 15mm can be used for a 12mm tablet height within the die and an insertion depth of 2mm for the upper punch.
[0127] The taper angle of the mold is typically 0.1° to 0.6°, and the size increase of the upper mold hole is preferably 0.03 mm to 0.2 mm, particularly preferably 0.05 mm to 0.14 mm. The increase in size can be mathematically derived from the taper angle and the taper depth.
[0128] In tablet molds with channels, the compression tool includes a pin. The pin is fixed to a turntable such that it is positioned within the mold cavity where the tablet is formed, allowing it to exit the tablet channel. Similar to the mold, the pin does not move vertically during the compression cycle, unlike the upper and lower punches. The vertical plane of the upper end of the pin is equal to or slightly lower than the height of the upper surface of the mold. Especially when the tablet has curved sides and the lower punch surface is concave, the vertical plane of the upper end of the pin should be slightly lower than the level of the upper front side of the mold so that the pin does not protrude from the lower punch surface.
[0129] In tablet dies with channels, adhesion typically occurs on the pin surface, leading to disadvantages such as high ejection forces due to high friction at the pin-tablet interface. This problem is particularly pronounced in multi-channel dies with multiple pins. Typically, pins exhibit a higher tendency to adhere than the die walls and the tips of the downstroke line.
[0130] When a tablet mold has channels, the pin preferably has a slight taper of a defined length in the upper region. The tapered portion of the pin shows that the pin diameter gradually decreases towards the upper end of the pin. The main advantage of a tapered pin is that it is easier to eject after compression. Due to the embossing of the tapered pin, compression into a tablet at the tapered position of the pin results in a tablet channel with a slightly tapered inner surface. The diameter of the tablet channel decreases slightly from bottom to top along the axial direction. During the ejection phase, where the lower punch pushes the tablet upward in the mold while the pin and mold remain perpendicular, the tablet is easily ejected from the pin because the slight lifting of the tablet due to the tapered structure forces the tablet to separate from the pin. When the pin has no taper, the tablet will not separate from the pin, so the entire ejection process (i.e., pushing the tablet upward from the depth of compression to the upper end face of the mold) is subject to friction at the tablet-pin interface, resulting in high ejection force. Tapered pins are particularly advantageous when the tablet has multiple channels.
[0131] The length of the pin's taper should be chosen so that the formed tablet is primarily located in the tapered zone before ejection. To achieve this, the length of the pin's taper can be oriented by adding the height of the tablet within the die before elastic recovery (i.e., the minimum distance between the upper and lower punches) and the insertion depth of the upper punch. For example, a taper length of 12mm to 15mm can be used for a 12mm tablet height within the die and an insertion depth of 2mm for the upper punch.
[0132] The angle of the mold taper is typically 0.1° to 0.6°, and the reduction in the diameter of the top pin is preferably 0.05 mm to 0.3 mm, particularly preferably 0.1 mm to 0.2 mm. This reduction can be mathematically derived from the angle and length of the taper.
[0133] The industrial-scale production of tablets is preferably carried out on a rotary tableting machine. Commercially available rotary tableting machines can be used in this invention. Examples of rotary tableting machines are the Korsch XT-600HD, Korsch XT-600, Korsch TPR 700, Korsch TRP 1200, Korsch XL 400MFP, Kilian RX, and Kilian Synthesis.
[0134] Rotary tablet presses typically have two clamping rollers for performing two-stage compression, including pre-compression and main compression. The main compression pressure ranges from 5 MPa to 500 MPa, preferably from 8 MPa to 400 MPa, and particularly preferably from 10 MPa to 300 MPa. The pre-compression pressure is typically from 5% to 50% of the applied main compression pressure, preferably from 7% to 40%, and particularly preferably from 10% to 35%.
[0135] The pressing tool is selected based on the desired geometry of the pressing body. The size and shape of the pressing body, as well as the catalyst, are selected such that the catalyst body obtained from the pressing body can be suitably filled into the reactor tube. The catalyst obtained from the pressing body suitable for the catalyst according to the invention is preferably used in reactor tubes with a length of 6 m to 14 m and an inner diameter of 20 mm to 50 mm. Typically, the support consists of a single body with a maximum dimension ranging from 3 mm to 20 mm, for example, 4 mm to 15 mm, particularly 5 mm to 12 mm. The maximum span refers to the longest straight line between two points on the outer periphery of the support.
[0136] The shape of the compressive element is not particularly limited and can be any technically feasible shape, depending on the molding process. For example, the support can be a solid tablet or a hollow tablet, such as a hollow cylinder. In another embodiment, the support can be characterized by a multi-lobed structure. A multi-lobed structure refers to a cylindrical structure with multiple cavities, such as grooves or channels extending along the circumference of the cylinder along its height. Typically, the cavities are arranged substantially equidistantly around the circumference of the cylinder.
[0137] The pressure during tableting affects the compaction of the free-flowing feed mixture, thereby influencing, for example, the density and / or mechanical stability of the compressed body. In practice, it has proven useful to selectively adjust the lateral compressive strength of the tableted catalyst support by choosing an appropriate pressure and testing it with random samples. For the purposes of this invention, lateral compressive strength is the force required to break the tableted catalyst support located between two parallel flat plates, wherein the two parallel flat end faces of the catalyst support are perpendicular to the parallel flat plates.
[0138] To improve tableting performance, the free-flowing feed mixture can be further processed, for example by sieving, preheating, and / or pre-granulation, i.e., pre-compression. For pre-granulation, roller compactors, such as those from Fitzpatrick, can be used.
[0139] Further information on tableting, particularly regarding pregranulation, sieving, lubricants, and tools, can be found in WO2010 / 000720. For more information on tableting, see Powder Technology Handbook, Chapter 16: Tableting, K. Pitt and C. Sinka, Vol. 11, 2007, pp. 735–778.
[0140] Advantageously, tableting is performed as described in documents WO 2005 / 030393, DE 10 2008 040093A1, DE 10 2008040094A1 and WO 2007 / 017431. The temperature around the tableting machine is typically 25°C. Optionally, as a result of preliminary coarsening by compaction, the particle size of the precursor composition to be compacted (a finely separated, tightly packed dry mixture) is advantageously in the range of 100 μm to 2000 μm, preferably 150 μm to 1500 μm, particularly preferably 400 μm to 1250 μm, or 400 μm to 1000 μm, or 400 μm to 800 μm (molding aids mixed before compaction are not considered here).
[0141] Similar to molding equipment or molding methods used for pressing, the desired geometry of the resulting molded body is not limited in the method according to the invention.
[0142] A preferred ring geometry (the geometry of the uncalcined green body and the solid catalyst molded body grown therefrom by calcination are generally substantially the same) is a geometry of 5 mm × 5 mm × 2 mm (outer diameter × height (length) × inner diameter). This is because a catalyst fixed bed composed of rings of this geometry produces particularly low pressure loss when flowing through the reactant gas mixture of the catalyst fixed bed (especially in reaction tubes with an inner diameter of 22 mm to 30 mm). Low pressure loss is particularly advantageous when operating under high loads (high flow rates) of the reactant gas mixture catalyzed by the catalyst fixed bed in the fixed bed. Another preferred ring geometry (especially in reaction tubes with a smaller inner diameter (e.g., 20 mm), which has advantageous filling behavior) is a geometry of 5 mm × 3 mm × 2 mm (outer diameter × height (length) × inner diameter). However, of course, all geometries disclosed and recommended in WO 02 / 062737 and WO 2015 / 067656 are also suitable.
[0143] Especially in the case of annular precursor moldings (precursor moldings are also referred to as green bodies in the literature, regardless of their shape), molding compaction should advantageously be carried out in such a manner that the lateral compressive strength SDF of the resulting molding body is [missing information]. v (Compare DE 10 2008 040093A1, DE 10 2008 040094A1, and WO 2005 / 030393) The relation 5N≤SDF is satisfied. v ≤100N, preferably 8N≤SDF v ≤80N, and particularly preferred 12N≤SDF v ≤50N.
[0144] The experimental determination of transverse compressive strength is performed as described in documents WO 2005 / 030393 and WO 2007 / 017431. Of course, according to the invention, the annular green product recommended as in DE 10 2008 040093A1 is particularly preferred. In the described method for preparing the green body according to the invention, the end faces of the annular or annular molded body can be planar (two or only one of the two end faces) and outwardly (convex) bent (bent) (particularly compared to DE 10 2007 004961A1, EP 0 184790A2, DE 10 2008 040093A1 (e.g., paragraph
[0032] ) and DE 10 2008 04009A1 (e.g., paragraph
[0074] ) and the embodiments described individually in these documents). This convex curvature is generally not considered in determining / indicating the height of such a geometric molded body in this document. Rings or annular molded bodies with convex curved (bent) end faces (preferably with both end faces having the same curvature) are advantageous because a catalyst bed with a ring or annular molded body having convex curved (bent) end faces (otherwise having the same geometry) results in less pressure loss of the reactant gas mixture flowing through the catalyst bed than a catalyst bed with a ring or annular molded body having flat end faces (especially in catalyst beds in reaction tubes). This is particularly suitable for ring geometries of 5 mm × 5 mm × 2 mm (outer diameter × height (length) × inner diameter). The radius of this convex curvature is typically 0.4 to 5 times (e.g., 0.8 to 4 times, or 1.2 to 3 times, or 1.6 to 2.6 times) the cylindrical outer diameter of the catalyst ring. As previously mentioned, catalyst beds resulting in lower pressure losses are particularly advantageous when partial oxidation catalyzed by a catalyst bed operates under high loads on the reactant gas mixture (at high flow rates of the reactant gas mixture flowing through the catalyst bed).
[0145] A particularly advantageous ring geometry of molded bodies obtained by compressing finely separated precursor compositions (finely separated compact dry mixtures) satisfies the condition that height (length) / outer diameter = H / A = 0.3 to 1.5 or 1.2. H / a = 0.5 to 1.1 or 1.0 is particularly preferred. Furthermore, a ratio I / A (where I is the inner diameter of the ring geometry) of 0.3 to 1.5, preferably 0.6 to 1.1, is advantageous for annular or ring-shaped green bodies according to the invention.
[0146] The aforementioned ring geometry is particularly advantageous if it simultaneously possesses one of the favorable H / A ratios and one of the favorable I / A ratios. Such a possible combination is, for example, H / A = 0.3 to 1.5 or 1.2, and I / A = 0.3 to 1.5 or 0.6 to 1.1. Alternatively, H / A can be 0.5 to 1.1 or 1.0, and I / A can simultaneously be 0.3 to 1.5 or 0.6 to 1.1. Furthermore, it is advantageous for the relevant ring geometry when H is 2 mm to 7 mm, preferably 2 mm to 6 mm or 3 mm to 6 mm. Additionally, it is advantageous if A in the ring is 4 mm to 8 mm, preferably 4 mm to 6 mm. The preferred ring geometry has a wall thickness of 1 mm to 2 mm or up to 1.5 mm.
[0147] Therefore, the possible ring geometry according to the present invention is (A×H×I)5mm×5mm×2mm, or 5mm×2mm×2mm, or 5mm×3mm×2mm, 5mm×5mm×2.5mm, or 5mm×3mm×2.5mm, or 5.5mm×5.5mm×2.5mm, or 5.5mm×5.5mm×3mm, or 5mm×3mm×3mm, or 5.5mm×3mm×3.5mm, or 6mm×3mm×4mm, or 6mm×6mm×3mm, or 6mm×6mm×3.5mm, or 6.5mm×3mm×4.5mm, or 7mm×3mm×5mm, or 7mm×7mm×3mm, or 7mm×3mm×4mm, or 7mm×7mm×4mm.
[0148] Unless otherwise expressly stated, all information regarding the specific surface area of solids in this literature is based on measurements according to DIN 66131 (specific surface area of solids by gas adsorption (N2) according to Brunauer-Emmert-Teller (BET)).
[0149] All information regarding total pore volume and its pore size distribution in this literature is based on measurements using a mercury porosity determination method at 23°C using an Auto Pore V 9600 (MicroActiveInteractive Dara analysis software) device (range: 0.1-61000 psi) from Micromeritics GmbH, D-52072Aachen (evaluated using the Washburn equation, with a mercury contact angle of 140° and a mercury surface tension of 480 mN / m = 480 dyn / cm).
[0150] According to the invention, the precursor molded body advantageously has the lowest possible residual moisture content. This is especially true when the close mixing of various sources of elemental components other than oxygen is wet (particularly when it occurs by forming an aqueous mixture M).
[0151] The residual moisture content of a favorable green product is preferably ≤10% by weight, more preferably ≤8% by weight, even more preferably ≤6% by weight, and most preferably ≤4% by weight or ≤2% by weight (the determination of residual moisture can be carried out as described in "Die Bibliothek der Technik", Vol. 229, "Thermogravimetric Determination of Moisture in Materials", Basic and Practical Applications, Horst Nagel, Verlag Moderne Industrie, Modern Industrial Press (e.g., with the aid of Computrac MAX 5000XL from Arizona Instruments).
[0152] If the green product comes from an aqueous mixture M (so that its residual moisture content consists of water), then the determination of residual moisture is advantageous from an application technology point of view, using microwaves (e.g., using the LB 456 microwave system from BERTHOLD TECHNOLOGIES).
[0153] In this method, microwaves irradiate the material under study with very low power (0.1 mW) (due to the relatively low power, the latter's temperature remains essentially unchanged). Therefore, the material composition is polarized to varying degrees. In response, the microwaves lose velocity and energy. In this case, the influence of water molecules is significantly greater than that of other components, making selective determination of residual water content possible. This is because water molecules, due to their size and dipole nature, are able to follow alternating electromagnetic fields within the microwave frequency range particularly well through dipole orientation. They absorb energy and alter the alternating electromagnetic field through their electrical properties. The measurement principle is based on this field attenuation and field change. For example, a weak microwave field can be established on the sensor surface of a planar sensor, and the resonant frequency of the sensor system can be permanently analyzed by scanning the microwave frequency. If the water-containing analyte now passes through the sensor, the resonant frequency will shift, and its amplitude will attenuate. Both damping and resonant frequency shift increase with increasing water content, and therefore also with increasing bulk density of the analyte. However, in this case, the ratio of frequency shift to damping is a density-independent measure of the water content percentage, and thus crucial for humidity measurement. This ratio forms the so-called microwave humidity measurement, which represents the total humidity. Since the microwave resonance method is an indirect method of moisture measurement, calibration is required. In this calibration measurement, the sensor measures a material sample with a specified humidity. The microwave humidity measurement is then linked to the associated defined absolute humidity of the material to form the calibration of the measurement system. The measurement accuracy is typically ±0.1% moisture (e.g., moisture can be determined using a Sartorius PMD300PA online moisture meter).
[0154] In this context, the spray drying of a wet (e.g., aqueous) mixture M should be carried out in such a way that the resulting spray powder has the lowest possible residual moisture content.
[0155] Considering the aspects mentioned above, green products should be stored in ambient air (excluding atmospheric humidity) if possible (preferably in anhydrous inert gas or pre-dried air or in sealed containers until calcination).
[0156] Advantageously, the molding / forming and storage of finely separated, tightly dry mixtures have been carried out in the absence of ambient air (including atmospheric humidity) (e.g., under an N2 atmosphere).
[0157] Calcination of the green body is typically carried out at a temperature of at least 350°C or usually exceeding 350°C (calcination temperature). However, during calcination, the temperature generally does not exceed 650°C (in this document, the term calcination temperature refers to the temperature present in the calcined material (advantageously, the calcined material has the most uniform calcination temperature possible; this also applies to other calcination conditions)). During calcination, the temperature advantageously does not exceed 600°C, preferably does not exceed 570°C, and usually does not exceed 550°C. Furthermore, during the above-mentioned calcination process, temperatures exceeding 380°C are preferred, advantageously exceeding 400°C, particularly advantageously exceeding 420°C, and very particularly preferably exceeding 440°C. Calcination can also be divided into several parts in chronological order.
[0158] Prior to calcination, it is advantageous to perform a heat pretreatment at temperatures ≥120°C and <350°C, preferably ≥150°C and ≤320°C, and particularly preferably ≥170°C and ≤290°C. From an application perspective, it is advantageous to perform this heat pretreatment until the components contained in the composition to be heat-treated and decomposed into gaseous compounds under the heat treatment conditions have substantially (preferably completely) decomposed into gaseous compounds (this time can be, for example, 3 to 15 hours, typically 4 to 10 hours or 5 to 8 hours). Generally, on the one hand, the molar amount of cations other than metal ions contained in the subsequently calcined composition is ≤20 molar percentages (preferably ≤10 molar percentages) relative to the total molar amount of contained cations; on the other hand, the molar amount of cations contained in the same composition other than O... 2- The molar amount of other anions relative to the total molar amount of included anions is also ≤20 molar percentage (preferably ≤10 molar percentage).
[0159] Therefore, the favorable temperature window for the final calcination temperature is in the temperature range of 400°C to 600°C, or preferably in the temperature range of 420°C to 570°C, or particularly preferably in the temperature range of 450°C to 550°C.
[0160] The total duration of calcination typically exceeds 0.5 hours and often exceeds 2 hours. The processing time during calcination generally does not exceed 45 hours or 30 hours. Typically, the total calcination time is less than 25 hours. In principle, at higher calcination temperatures, a shorter calcination time is usually sufficient than at lower calcination temperatures. In an advantageous embodiment of the calcination according to the invention, the temperature does not exceed 550°C, and the calcination duration extends from >4 hours to ≤25 hours within the temperature window of ≥430°C and ≤550°C.
[0161] The entire heat treatment (including the decomposition stage) of the precursor composition (e.g., green body) can be carried out in an inert gas and oxidizing atmosphere, such as air (or other mixtures of inert gases and molecular oxygen), and in a reducing atmosphere (e.g., a mixture of inert gases, NH3, CO and / or H2, or methane). Of course, heat treatment can also be carried out under a vacuum. The atmosphere can also be variable during heat treatment.
[0162] Heat treatment (especially the calcination stage) is preferably carried out in an oxidizing atmosphere. From an application perspective, it mainly consists of stagnant or (preferably) moving air (particularly preferably an airflow passing through the composition to be heat-treated (calcined material)). However, the oxidizing atmosphere can also consist of, for example, a mixture of 25 volume percent N2 and 75 volume percent air, or 50 volume percent N2 and 50 volume percent air, or 75 volume percent N2 and 25 volume percent air (a treatment atmosphere of 100 volume percent N2 is also possible).
[0163] In principle, heat treatment (e.g., calcination) of the precursor composition (e.g., green body) can be carried out in various types of furnaces, such as heatable circulating air chambers (circulating air furnaces, e.g., circulating air shaft furnaces), tray furnaces, rotary kilns, belt calcining furnaces, or shaft furnaces. According to the invention, heat treatment (e.g., calcination) is advantageously carried out in a belt calcining apparatus, as recommended by DE 100 46957A1 and WO 02 / 24620. In this case, the formation of hot spots within the material to be treated (within the calcining material) is largely avoided because, with the aid of a fan, the increased volumetric flow rate of the calcining atmosphere through the permeable conveyor belt carrying the calcining material passes through the calcining material (this ensures the most uniform calcination temperature possible within the calcining material).
[0164] In the context of heat treatment of the precursor composition (e.g., green body) as described above, the commonly used molding aids can either remain in the resulting catalyst mold or undergo thermal and / or chemical decomposition to form gaseous compounds (e.g., CO, CO2), escaping at least partially in gaseous form from the latter. The molding aids remaining in the catalyst mold essentially serve only as diluents for the active material in its catalytic application. Essentially, the heat treatment can be carried out as described in US2005 / 0131253.
[0165] Typically, the lateral compressive strength of the annular solid catalyst molded body that can be obtained according to the present invention, as described, is 4N to 16N, usually 5N to 14N or 6N to 12N.
[0166] The specific (BET) surface area of the solid catalyst molded body is advantageously 2 m². 2 / g to 20m 2 / g or up to 15m 2 / g, preferably 3m 2 / g to 10m 2 / g, with 4m being the preferred choice 2 / g to 8m 2 / g. According to the invention, the associated total pore volume (mercury porosity method) is advantageously 0.33 cm³. 3 / g to 0.60cm 3 Within the range of / g, preferably within 0.36cm 3 / g to 0.54cm 3 Within the range of / g, it is particularly preferred to be within 0.38cm. 3 / g to 0.50cm 3 Within the range of / g.
[0167] If the pore size is plotted in μm on the horizontal axis, and in cm... 3 Aperture in g versus cm 3 Plotting the logarithm of the differential contribution of the total pore volume in units of g on the ordinate, the solid catalyst molded according to the present invention typically exhibits a substantially unimodal distribution (with only a distinct maximum value). If the contribution of pores with a pore radius ≤0.1 μm to the total pore volume is ≤0.05 cm⁻¹ 3 / g, resulting in exceptionally good overall target product selectivity (e.g., in the case of heterogeneous catalytic partial oxidation of propylene to acrolein and / or acrylic acid). In such cases, the contribution of these relatively narrow pores to the total pore volume is >0.05 cm⁻¹. 3 In the case of / g, according to the present invention, this contribution can be advantageously reduced by increasing the calcination time and / or calcination temperature.
[0168] Furthermore, if the contribution of pores with pore radii in the range of 0.1 μm to 1 μm to the total pore volume is 85 to 99% of the total pore volume, advantageously 87 to 97%, and particularly preferably 89 to 95%, it is shown to be beneficial for increasing the overall selectivity of the target product.
[0169] Of course, solid catalyst molded bodies can also be used together with diluted inert materials for the partial gas-phase oxidation of heterogeneous catalysis. Suitable inert diluent materials are especially elemental oxides calcined at high temperatures and therefore having relatively few pores, such as alumina, silica, thorium dioxide, and zirconium dioxide. However, finely separated silicon carbide or finely separated silicates such as magnesium silicate and aluminum silicate or talc can also be used for the above purposes. For example, it is advantageous to grind the calcined active composition into a finely separated powder. This powder is then mixed with a finely separated diluent material, and the resulting mixed powder is shaped into a geometric molded body using the molding method proposed in this document (preferably by tableting). The latter is then converted into the associated solid catalyst molded body through subsequent further calcination. Of course, the finely separated inert diluent material can also be incorporated into a wet (e.g., aqueous) mixture M, for example, before drying. Furthermore, the finely separated inert diluent material can be incorporated into a finely separated dry mixture. However, this method is less preferred according to the invention.
[0170] In particular, the solid catalyst molded body prepared according to the advantageous preparation method is distinguished by the fact that it is essentially free of local centers of elemental oxides. Instead, these elements are largely composed of complex mixed oxymolybdates containing Bi, Fe, and Mo. This has proven advantageous because, in the context of relevant heterogeneous catalytic partial oxidation, undesirable complete combustion of the organic reactive gas mixture components is minimized according to the invention.
[0171] Furthermore, from the perspective of making the most efficient use of materials, the method described in WO 2010 / 066645 is advantageous for the preparation of solid catalysts.
[0172] The solid catalyst molded body according to the invention is applicable not only to the heterogeneous catalytic partial oxidation of propylene to acrolein, but also generally applicable to the heterogeneous catalytic partial gas-phase oxidation of alkanes, alkanols, alkenes and / or alkenes having 3 to 6 carbon atoms (in this document, partial oxidation should be specifically understood as those reactions of organic compounds in the presence of molecular oxygen, wherein the organic compound to be partially oxidized contains at least one more chemically bonded oxygen atom after the reaction is completed than before partial oxidation). However, in this document, the term partial oxidation should also include oxidative dehydrogenation and partial ammonia oxidation, i.e., partial oxidation in the presence of ammonia.
[0173] The solid catalyst molded body according to the present invention is particularly suitable for catalyzing the partial gas-phase oxidation of propylene to acrolein, the partial gas-phase oxidation of isobutylene to methacrolein, and the partial gas-phase ammoxidation of propylene to acrylonitrile and the partial gas-phase ammoxidation of isobutylene to methacrolein.
[0174] As previously described, the first stage of the two-stage heterogeneous catalytic partial gas-phase oxidation of propylene (isobutylene and / or tert-butanol) to acrolein (methacrylaldehyde) forms the first stage of the heterogeneous partial gas-phase oxidation of propylene (isobutylene and / or tert-butanol) to acrylic acid (methacrylic acid), as illustrated in WO 2006 / 42459.
[0175] Therefore, the formation of acrylic acid (methacrylic acid) byproducts associated with the heterogeneous catalytic partial gas-phase oxidation of propylene (isobutylene) to acrolein (methacrylaldehyde) is generally undesirable and is often included in the formation of the desired valuable product.
[0176] The above conditions are particularly applicable to the annular solid catalyst molded body according to the present invention.
[0177] Heterogeneous catalytic partial oxidation (especially the partial oxidation of propylene to acrolein) can be exemplified in references such as DE 102007 004961A1, WO 02 / 49757, WO 02 / 24620, DE 10 2008040093A1, WO 2005 / 030393, EP 0575 897 A1, WO 2007 / 082827, WO 2005 / 113127, WO 2005 / 047224, WO 2005 / 042459, WO2007 / 017431, DE 10 2008 042060A1, WO 2008 / 087116, DE 10 2010 048405A1, DE 102009047291A1, and DE 10 Similar catalysts described in 2008 042064A1, DE 10 2008 042061A1, WO 2015 / 067656 and DE 102008 040094A1 (in particular, the process can be carried out in a manner corresponding to the exemplary embodiments in these documents).
[0178] However, the advantages of solid catalyst molding bodies (especially ring-shaped ones) as described above also exist when the catalyst charge in the reactor is loaded with propylene, isobutylene, and / or tert-butylene contained in the reactant gas inlet mixture. Butanol (or its methyl ether) ≥130 Nl / L catalyst charge·h, or ≥140 Nl / L·h, or ≥150 Nl / L·h, or ≥160 Nl / L·h (in this literature, pre-filling and / or post-filling of purely inert materials are not considered part of the catalyst charge; the volume of the catalyst charge (fixed catalyst bed) is its volume in the reactor). Under normal conditions, the above-mentioned catalyst charge will be ≤600 Nl / L·h, typically ≤500 Nl / L·h, typically ≤400 Nl / L·h, or ≤350 Nl / L·h. Loads in the range of ≥160 Nl / l·h or ≥180 Nl / l·h to ≤300 Nl / l·h or ≤250 Nl / l·h or ≤200 Nl / l·h are particularly advantageous.
[0179] In this literature, the load of the reactant gas inlet mixture in the catalyst fixed bed is understood as the amount of reactant gas inlet mixture in standard liters (= Nl; the volume in liters that the corresponding amount of reactant gas inlet mixture would occupy under standard conditions of 0 °C and 1 atm (1.01 bar), based on the volume of its bed (excluding the bed portion of purely inert material), i.e., based on its bed volume, per hour (-> unit = Nl / l·h). In this literature, standard volume units, such as Nl or Nm, are used. 3 "" always refers to the standard conditions of 0°C and 1 atm (1.01 bar) (unless otherwise explicitly stated).
[0180] The load can also be based on only one component of the reactant gas inlet mixture (e.g., only based on the organic starting compound to be partially oxidized). Then, the volume of that component (e.g., the partially oxidized organic starting compound) supplied per hour to the catalyst stationary bed (the catalyst charge of the reactor) is based on the volume of its bed.
[0181] Of course, the (e.g., cyclic) solid catalyst molded bodies available according to the invention can be used as catalysts for the partial oxidation of propylene to acrolein or isobutylene and / or tert-butylene. The conversion of butanol (or its methyl ether) to methacrolein can also be advantageously operated according to the invention, even if the catalyst charge is ≤130 Nl / l·h, or ≤120 Nl / l·h, or ≤110 Nl / l·h, or ≤100 Nl / l·h, or ≤90 Nl / l·h. However, typically, this charge is ≥20 Nl / l·h, or ≥30 Nl / l·h, or ≥40 Nl / l·h, or ≥50 Nl / l·h, or ≥60 Nl / l·h, or ≥70 Nl / l·h, or ≥80 Nl / l·h.
[0182] In principle, the catalyst load in the reactor (catalyst fixed bed) filled with the starting compound to be partially oxidized (propylene, isobutylene, and / or tert-butanol (or its methyl ether)) can be adjusted using two adjusting screws:
[0183] a) Loading the catalyst charge with the reactant gas inlet mixture (the reactant gas mixture supplied to the catalyst fixed bed), and / or
[0184] b) The content of the reactant gas inlet mixture and the starting compound to be partially oxidized.
[0185] The (e.g., annular) solid catalyst molded bodies available according to the present invention are also particularly suitable for use when the load is higher than 130 Nl / l·h, and the load adjustment is mainly carried out by the aforementioned adjusting screw a).
[0186] Typically, for example, the propylene portion (isobutylene portion or tert-butanol portion (or methyl ether portion)) in the reactant gas inlet mixture is substantially independent of the catalyst charge load and ranges from 4 to 10 volume percent, typically from 5 to 9 volume percent, or from 5.5 to 8.0 volume percent, or from 6.0 to 7.5 volume percent (in each case based on the total volume (flow) of the reactant gas inlet mixture flowing into the catalyst fixed bed).
[0187] The gas-phase partial oxidation method (substantially independent of the load) using a solid catalyst molded body (e.g., cyclic) according to the invention, which can be obtained as described above, is generally carried out with the (organic) compound to be partially oxidized (e.g., propylene): the volume ratio of oxygen to inert (inert) gas (including water vapor) in the reaction gas inlet mixture is 1:(1.0 to 3.0):(5 to 25), preferably 1:(1.5 to 2.3):(10 to 20).
[0188] In this context, an inert gas (or inert gas) is understood to be a gas that remains chemically unchanged for at least 95 molar percentage, preferably at least 98 molar percentage, during the partial oxidation of the reactant gas mixture in a single pass through the catalyst bed.
[0189] In the above-mentioned reactant gas inlet mixture, the inert gas may consist of molecular nitrogen of ≥20, ≥30, ≥40, ≥50, ≥60, ≥70, ≥80, ≥90, or ≥95 volume percentages.
[0190] However, at higher catalyst charge loads in the reactor (e.g., ≥150 Nl / L·h), it is recommended (but not mandatory) to use inert dilution gases with increased molar heat and / or thermal conductivity, such as propane, ethane, methane, pentane, butane, CO2, CO, water vapor, and / or inert gases, for the inlet mixture of reactant gases. However, these inert gases and mixtures thereof can generally also be used at lower catalyst charge loads with organic compounds to be partially oxidized. Recycled gases can also be used as dilution gases. Recycled gases refer to the residual gases remaining after the target compound has been substantially selectively separated from the partially oxidized product gas mixture. It should be taken into consideration that the partial oxidation to acrolein or methacrolein using a toroidal solid catalyst molded according to the invention can only be the first stage of a two-stage partial oxidation of acrylic acid or methacrylic acid, which are the actual target compounds, such that the formation of the circulating gas typically occurs only after the second stage (typical circulating gas compositions for the heterogeneous catalytic partial oxidation of propylene to acrolein and / or acrylic acid are shown in DE 102 32 482A1 in paragraphs
[0063] and
[0075] ). In the case of such two-stage partial oxidation, the product gas mixture of the first stage is typically supplied to the second partial oxidation stage after cooling and / or a secondary addition of oxygen (typically as air).
[0191] In the case of partial oxidation of propylene to acrolein, using a (e.g., cyclic) solid catalyst molded according to the invention, which is available as described above, the typical composition of the reaction gas inlet mixture measured at the reactor inlet (regardless of the selected load) may include, for example, the following components.
[0192] 6% to 6.5% propylene by volume.
[0193] 1% to 3.5% H₂O by volume.
[0194] 0.8% to 1.7% CO x ,
[0195] Acrolein, ranging from 0.015% by volume to 0.04%
[0196] Oxygen at a volume percentage of 9.4 to 12.3, and residual molecular nitrogen at a volume percentage;
[0197] or
[0198] 5.6% propylene by volume
[0199] 1.4 volume percentage of H2O
[0200] 1.2 Volume percentage CO x ,
[0201] 10.2% by volume oxygen and
[0202] The residual amount is molecular nitrogen by volume percentage;
[0203] The former composition is particularly suitable for propylene loading ≥130 Nl / l·h, while the latter composition is particularly suitable for propylene loading <130 Nl / l·h, especially ≤100 Nl / l·h (e.g., for starting up partial oxidation of a fixed-bed catalyst).
[0204] Alternatively, the reaction gas inlet mixture of the composition according to Example 1 of EP 0 990 636 A1, or Example 2 of EP 0 990 636 A1, or Example 3 of EP 1 106 598 A2, or Example 26 of EP 1 106 598 A2, or Example 53 of EP 1 106 598 A2, or the embodiment of WO 2021 / 013640 can also be used for the partial oxidation of propylene to acrolein according to the present invention.
[0205] The solid catalyst molded bodies according to the invention, such as rings, that are available as described above are also applicable to the methods of DE 10246 119A1 and DE 102 45 585A1.
[0206] When using a solid catalyst molded according to the invention (e.g., a ring-shaped one) as described, the reaction temperature for the heterogeneous catalytic partial oxidation of propylene to acrolein according to the invention is typically 300°C to 450°C, or up to 400°C, or up to 380°C. A particularly preferred reaction temperature window is 305°C to 345°C. This also applies to the case of methacrolein as the target compound.
[0207] For the above partial oxidation, the reaction pressure is typically 0.5 bar to 4 bar or up to 3 bar, or preferably 1.1 bar or 1.5 bar to 4 bar or up to 3 bar (unless otherwise explicitly stated, the pressure referred to in this document is always absolute pressure).
[0208] In the partial oxidation according to the invention described above, the total load of the catalyst charge having the reactant gas inlet mixture is typically from 1000 Nl / l·h to 10000 Nl / l·h, typically from 1500 Nl / l·h to 5000 Nl / l·h, and typically from 2000 Nl / l·h to 4000 Nl / l·h.
[0209] Suitable propylene for use in the reactant gas inlet mixture, particularly polymer-grade and chemical-grade propylene, as described, for example, in WO 2004 / 007405.
[0210] Air (optionally along with circulating gas) is typically used as the oxygen source.
[0211] In the simplest case, as described in DE 44 31 957 A1, EP 0 700 714 A1 and EP 0 700893A1, partial oxidation using the solid catalyst molded body (e.g., ring-shaped) according to the invention, which is available as described above, can be carried out, for example, in a single-zone multi-contact tube fixed-bed reactor.
[0212] In the aforementioned tube bundle reactors, the contact tubes are typically made of ferritic steel and generally have a wall thickness of 1 mm to 3 mm. Their inner diameter is typically 20 mm to 30 mm, and usually 21 mm to 26 mm. Typical contact tube lengths are, for example, 3.50 m, 4.00 m, or 4.50 m. The number of contact tubes housed in the tube bundle container conveniently reaches at least 1000, preferably at least 5000. The number of contact tubes housed in the reaction vessel is typically 15000 to 40000. Tube bundle reactors with more than 45000 contact tubes are exceptions. Under normal circumstances, the contact tubes are arranged in a uniform distribution within the vessel, wherein this distribution is conveniently chosen such that the distance between the central inner axes of the nearest contact tubes (the so-called contact tube spacing) is 35 mm to 45 mm (see EP 0 468 290 B1).
[0213] However, partial oxidation can also be carried out in multi-zone (e.g., "dual-zone") multi-contact tube fixed-bed reactors, as recommended by DE199 10 506A1, DE 103 13 213A1, DE 103 13 208A1, and EP 1 106 598A2, particularly when the catalyst load is increased in the multi-contact tube reactor to which the organic compound to be partially oxidized is charged. In the case of dual-zone multi-contact tube fixed-bed reactors, typical contact tube lengths are 3.50 m, 4.00 m, or 4.50 m. Everything else is essentially the same as described for single-zone multi-contact tube fixed-bed reactors. In each tempering zone of a single-zone or multi-zone multi-contact tube fixed-bed reactor (a single-zone multi-contact tube fixed-bed reactor has only one tempering zone), the heat exchange medium is directed around the contact tube where the catalyst charge (catalyst fixed bed) is located. Suitable melts are, for example, melts of salts such as potassium nitrate, potassium nitrite, sodium nitrite, and / or sodium nitrate, or melts of low-melting-point metals such as sodium, mercury, and alloys of various metals. The flow rate of the heat exchange medium within the appropriate tempering zone is typically selected such that the temperature of the heat exchange medium rises from 0°C to 15°C from its entry point into the tempering zone to its exit point, typically 1°C to 10°C, or 2°C to 8°C, or 3°C to 6°C.
[0214] Considering the corresponding tempering zone, the inlet temperature of the heat exchange medium, which can be transported co-currently or counter-currently with the reactant gas mixture, is preferably selected as recommended in documents EP 1 106 598 A2, DE 199 48 523 A1, DE 19948 248 A1, DE 103 13209 A1, EP 0 700 714 A1, DE 103 13 208 A1, DE 10313 213 A1, WO 00 / 53557, WO 00 / 53558, WO 01 / 36364, WO 00 / 53557, and other documents cited as prior art in these documents. Within the tempering zone, the heat exchange medium is preferably guided in a zigzag manner. When considering the longitudinal portion of the catalytically active (not purely inert) part of the fixed-bed catalyst, located within the tempering zone, the difference between the highest and lowest temperatures of the heat exchange medium within the tempering zone should advantageously be ≥0°C and ≤5°C (preferably very small). Typically, multi-contact tube fixed-bed reactors also include heat pipes (heat pipes and reaction tubes housed in the same fixed bed) for determining the temperature of the reactant gas in the catalyst bed. Advantageously, the inner diameter of the heat pipes and the diameter of the receiving sleeve (heat sheath) for the thermocouples, located inside the heat pipes and extending parallel to their longitudinal axis, are selected such that, in the case of the heat pipes and the working tubes, the ratio of the volume generating the heat of reaction to the heat dissipation surface is the same or only slightly different.
[0215] Based on the same GHSV (the intensity of the volumetric flow rate of the reactant gas mixture entering the pipe divided by the volume of the catalyst fixed bed located in the pipe), the pressure losses in the working pipe and the heat pipe should be identical. The pressure loss in the heat pipe can be compensated, for example, by adding split catalyst to the solid catalyst mold. This compensation advantageously occurs uniformly along the entire length of the heat pipe. Furthermore, the heat pipe can be filled as described in EP 0 873 783 A1.
[0216] As previously stated, for the preparation of the catalyst charge in the contact tube, only solid catalyst molds (e.g., toroidal) obtainable as described can be used, or a substantially homogeneous mixture of a solid catalyst mold (e.g., toroidal) obtainable as described and a mold that is essentially inert relative to the partial gas-phase oxidation of the heterogeneous catalysis can be used. Suitable materials for such inert molds are, for example, porous or non-porous alumina, silica, zirconium dioxide, silicon carbide, silicates such as magnesium silicate or aluminum silicate, and / or talc (e.g., C220 from CeramTec, DE).
[0217] The geometry of this inert dilution molded body is whatever is desired. That is, it can be, for example, a sphere, a polygon, a solid cylinder, or it can be a ring, as in the case of a ring-shaped catalyst molded body. Typically, inert dilution molded bodies are those whose geometry corresponds to the geometry of the catalyst molded body to which it is to be diluted. However, the geometry of the catalyst molded body can also be varied along the catalyst charge, or catalyst molded bodies with different geometries can be used in a substantially homogeneous mixture. In a less preferred approach, the active mass of the catalyst molded body can also be varied along the catalyst charge.
[0218] Typically, catalyst charges are advantageously designed such that the volumetric activity (i.e., normalized to unit volume) remains constant or increases (continuously, abruptly, or gradually) in the direction of flow of the reactant gas mixture.
[0219] The reduction in volumetric activity can be achieved in a simple manner, for example, by uniformly diluting a basic amount of solid catalyst molded according to the invention (e.g., a ring) with an inert diluent molded body. The higher the proportion of the selected diluent molded body, the lower the active material or catalyst activity contained in a given volume of charge. However, reduction can also be achieved by changing the geometry of the solid catalyst molded body available according to the invention, thereby reducing the amount of active material contained per unit volume inside the reaction tube.
[0220] For multiphase catalytic gas-phase partial oxidation having solid catalyst molded bodies (e.g., annular) available as described above, the catalyst charge is preferably uniformly designed along its entire length, having only one type of solid catalyst molded body, or structured as follows. At the reactor inlet, in each case, a substantially homogeneous mixture of solid catalyst molded bodies and inert diluent molded bodies (both preferably having substantially the same geometry) is placed over 10% to 60%, preferably 10% to 50%, particularly preferably 20% to 40%, and very particularly preferably 25% to 35% of the total length of the catalyst charge (i.e., a length of, for example, 0.70 m to 1.50 m, preferably 0.90 m to 1.20 m), wherein the weight percentage of the diluent molded body (the bulk density of the catalyst molded body and the diluent molded body is typically only slightly different) is typically 5% to 40%, or 10% to 40%, or 20% to 40%, or 25% to 35% by weight. Following the first loading section, advantageously, until the end of the length of the catalyst loading (i.e., for example, at a length of 1.00m to 3.00m or 1.00m to 2.70m, preferably 1.40m to 3.00m or 2.00m to 3.00m), or only to a lesser degree than that in the first section (e.g., in the first section), or very particularly preferably a single (undiluted) bed of the same (e.g., toroidal) solid catalyst molded body also used in the first section. Of course, a constant dilution can also be selected throughout the loading. Furthermore, in the first section, only (e.g., toroidal) solid catalyst molded bodies with a low active material density relative to their space requirements can be loaded, and in the second section, solid catalyst molded bodies with a high active material density relative to their space requirements (e.g., toroidal) relative to their space requirements, obtainable according to the invention (e.g., 6.5mm × 3mm × 4.5mm [outer diameter × height × inner diameter] in the first section, and 5 × 2 × 2mm [A × H × I] in the second section) can be loaded.
[0221] In the flow direction of the reactant gas mixture, the bed of inert molded body can be positioned upstream of the actual catalyst fixed bed, with the aim of, for example, raising the inlet temperature of the reactant gas mixture to the temperature of the heat exchange medium.
[0222] Furthermore, according to the teachings of existing technologies (e.g., WO 2012 / 049246), in the case of heterogeneous catalytic partial oxidation of propylene to acrolein (or in the case of heterogeneous catalytic partial oxidation for the preparation of methacrolein), the catalyst charge (especially freshness) and process conditions of the catalytic partial oxidation are preferably selected (configured) in such a way that, in partial oxidation operations at any location in the catalyst fixed bed, the difference between the temperature at that location and the temperature of the heat exchange medium at that level is not ≥120°C. Advantageously, this temperature difference is positive at each point, but ≤100°C (especially 40°C to 100°C), and particularly advantageously ≤90°C (especially 50°C to 90°C). However, in principle, such a (positive) temperature difference can also be ≤50°C or ≤40°C. Furthermore, this design is preferably such that when the temperature of the heat exchange medium increases by 1°C at each point in the catalyst fixed bed, the temperature difference increases by >0°C but ≤+9°C, more preferably ≤+7°C, preferably ≤+5°C, and particularly preferably ≤+3°C (see also EP 1 106 598 A1).
[0223] Furthermore, the heterogeneous catalytic partial oxidation for the preparation of acrolein (from propylene) or methacrolein (from the C4 precursor compounds mentioned in this document) can be advantageously carried out using a ring-shaped solid catalyst mold prepared according to the invention, which corresponds exactly to the statement in WO 2015 / 067656.
[0224] In general, when using a solid catalyst molded body (e.g., a ring-shaped) as a catalyst for the partial oxidation of acrolein or methacrolein, the catalyst charge, initial reactant gas mixture, loading, and reaction temperature are typically selected such that the conversion of the partially oxidized organic compound (propylene, isobutylene, tert-butanol, or its methyl ether) is at least 90 mol% or at least 92 mol%, preferably at least 93 mol%, at least 94 mol%, at least 95 mol%, or at least 97 mol%, but typically ≤99 mol%, when the reactant gas mixture passes through the catalyst charge once. In this case, the selectivity for the valuable product (the sum of acrolein and acrylic acid or the sum of methacrolein and methacrylic acid) is typically ≥80 mol%, or ≥85 mol%, or ≥90 mol%.
[0225] Finally, it can be noted that the solid catalyst molded body according to the invention, which is available as described above, also exhibits favorable fracture behavior during reactor filling.
[0226] A fresh catalyst charge (fixed-bed catalyst) comprising a (e.g., annular) solid catalyst molded body available according to the invention can be started, for example as described in DE 103 37 788A1 or DE 10 2009 047291A1.
[0227] The formation of the solid catalyst molded body obtainable according to the present invention can be accelerated by increasing the load of the reactant gas inlet mixture on the catalyst charge at a substantially constant conversion rate.
[0228] Furthermore, the solid catalysts available according to the present invention are generally suitable for catalytically oxidizing the gas-phase fraction (ammonia) of alkanols, alkanal aldehydes, alkenes, alkanes and alkenal aldehydes containing 3 to 6 (i.e. 3, 4, 5 or 6) carbon atoms to, for example, unsaturated aldehydes and / or carboxylic acids and corresponding nitriles, as well as the gas-phase catalytic oxidative dehydrogenation of the aforementioned organic compounds containing 3, 4, 5 or 6 carbon atoms.
[0229] The industrial-scale preparation of the solid catalyst molded body according to the invention is conveniently carried out in a manner similar to that described in DE 10 2008040093A1 and DE 10 2008 040094A1 (particularly advantageously as described in the exemplary embodiments of these documents).
[0230] Therefore, this application specifically includes the following embodiments according to the invention:
[0231] Therefore, the present invention specifically includes the following embodiments according to the invention:
[0232] 1. A method for preparing a solid catalyst mold for the gas-phase oxidation of olefins and / or alcohols to α,β-unsaturated aldehydes and / or α,β-unsaturated carboxylic acids, wherein the solid catalyst mold comprises at least the elements molybdenum, bismuth, iron, and cobalt, wherein,
[0233] a) The aqueous solution or aqueous suspension is produced from each of at least one source of the elemental composition molybdenum, bismuth, iron, cobalt, and optionally at least one source of the elemental composition nickel.
[0234] b) Powder P is produced by drying the aqueous solution or aqueous suspension obtained in a) and optionally pulverizing it.
[0235] c) The powder P obtained in b) is optionally mixed with one or more additives, and after uniform mixing and optional compaction, is pressed into a precursor molded body having a cylindrical structure, and
[0236] d) The precursor molded body obtained in c) is heat-treated to form the solid catalyst molded body.
[0237] The characteristic feature is that the pressure during the compression process in c) is selected such that the density of the precursor molded body is 1.70 g / cm³. 3 Up to 2.30 g / cm 3, wherein the density of the precursor molded body is the quotient of its mass and geometric volume, and the weight loss during heat treatment in d) is 25% to 40% by weight.
[0238] 2. The method according to embodiment 1, characterized in that the pressure during the compression period in c) is selected such that the density of the precursor molded body is 1.72 g / cm³. 3 Up to 2.28 g / cm 3 .
[0239] 3. The method according to embodiment 1 or 2, characterized in that the pressure during the compression period in c) is selected such that the density of the precursor molded body is 1.74 g / cm³. 3 Up to 2.26 g / cm 3 .
[0240] 4. The method according to any one of embodiments 1 to 3, characterized in that, in c)
[0241] The pressure during compression resulted in a precursor molded body density of 1.76 g / cm³. 3 Up to 2.24 g / cm 3 .
[0242] 5. The method according to any one of embodiments 1 to 4, characterized in that, in c)
[0243] The pressure during compression resulted in a precursor molded body density of 1.78 g / cm³. 3 Up to 2.22 g / cm 3 .
[0244] 6. The method according to any one of embodiments 1 to 5, characterized in that, in c)
[0245] The pressure during compression resulted in a precursor molding density of 1.80 g / cm³. 3 Up to 2.20 g / cm 3 .
[0246] 7. The method according to any one of embodiments 1 to 6, characterized in that the weight loss during heat treatment in d) is 26% to 39% by weight.
[0247] 8. The method according to any one of embodiments 1 to 7, characterized in that the weight loss during heat treatment in d) is 27% to 38% by weight.
[0248] 9. The method according to any one of embodiments 1 to 8, characterized in that the weight loss during heat treatment in d) is 28% to 38% by weight.
[0249] 10. The method according to any one of embodiments 1 to 9, characterized in that the weight loss during heat treatment in d) is 29 to 37 percent by weight.
[0250] 11. The method according to any one of embodiments 1 to 10, characterized in that the weight loss during heat treatment in d) is 30 to 35 percent by weight.
[0251] 12. The method according to any one of embodiments 1 to 11, characterized in that the cylindrical shape
[0252] The structure is
[0253] i) A cylindrical body with a continuous central circular opening in the longitudinal direction, or
[0254] ii) A three-fold concave cylindrical body having three circular continuous openings evenly arranged in the longitudinal direction.
[0255] 13. The method according to any one of embodiments 1 to 12, characterized in that the cylindrical structure is a hollow cylinder.
[0256] 14. The method according to any one of embodiments 1 to 13, characterized in that the molybdenum content of the solid catalyst molded body, calculated as MoO3, is 45% to 75% by weight.
[0257] 15. The method according to any one of embodiments 1 to 14, characterized in that the molybdenum content of the solid catalyst molded body, calculated as MoO3, is 50 to 70% by weight.
[0258] 16. The method according to any one of embodiments 1 to 15, characterized in that the molybdenum content of the solid catalyst molded body, calculated as MoO3, is 55 to 65% by weight.
[0259] 17. The method according to any one of embodiments 1 to 16, characterized in that the bismuth content of the solid catalyst molded body, calculated as Bi2O3, is from 1 to 20% by weight.
[0260] 18. The method according to any one of embodiments 1 to 17, characterized in that the bismuth content of the solid catalyst molded body, calculated as Bi2O3, is 2 to 15% by weight.
[0261] 19. The method according to any one of embodiments 1 to 18, characterized in that the bismuth content of the solid catalyst molded body, calculated as Bi2O3, is 3 to 10% by weight.
[0262] 20. The method according to any one of embodiments 1 to 19, characterized in that the iron content of the solid catalyst molded body, calculated as Fe2O3, is 2 to 12% by weight.
[0263] 21. The method according to any one of embodiments 1 to 20, characterized in that the iron content of the solid catalyst molded body, calculated as Fe2O3, is 3 to 11% by weight.
[0264] 22. The method according to any one of embodiments 1 to 21, characterized in that the iron content of the solid catalyst molded body, calculated as Fe2O3, is 4 to 10% by weight.
[0265] 23. The method according to any one of embodiments 1 to 22, characterized in that the cobalt and nickel content of the solid catalyst molded body, calculated as CoO and NiO, is a total of 9 to 30 percent by weight.
[0266] 24. The method according to any one of embodiments 1 to 23, characterized in that the cobalt and nickel content of the solid catalyst molded body, calculated as CoO and NiO, is a total of 12 to 27 percent by weight.
[0267] 25. The method according to any one of embodiments 1 to 24, characterized in that the cobalt and nickel content of the solid catalyst molded body, calculated as CoO and NiO, is a total of 15 to 24 weight percent.
[0268] 26. The method according to any one of embodiments 1 to 25, characterized in that the solid catalyst molded body further comprises elemental potassium and / or silicon.
[0269] 27. A solid catalyst mold having a cylindrical structure for gas-phase oxidation of olefins and / or alcohols to α,β-unsaturated aldehydes and / or α,β-unsaturated carboxylic acids, obtainable according to the methods of Embodiments 1 to 26, wherein the solid catalyst mold comprises at least the elements molybdenum, bismuth, iron, and cobalt, and wherein the density of the solid catalyst mold is 1.20 g / cm³. 3 Up to 1.70 g / cm 3 The density of the solid catalyst molded body is the quotient of its mass and geometric volume, and the total pore volume of the solid catalyst molded body is 0.33 cm³. 3 / g to 0.60cm 3 / g, and the pore volume of the solid catalyst molded body in the range of 0.1μm to 1μm is 85% to 99% of the total pore volume, wherein the total pore volume and the pore volume in the range of 0.1μm to 1μm are determined by mercury porosity determination method.
[0270] 28. The solid catalyst molded body according to Embodiment 27, wherein the density of the solid catalyst molded body is 1.22 g / cm³. 3 Up to 1.68 g / cm 3 .
[0271] 29. The solid catalyst molded body according to embodiment 27 or 28, wherein the density of the solid catalyst molded body is 1.24 g / cm³. 3 Up to 1.66 g / cm 3 .
[0272] 30. A solid catalyst molded body according to any one of embodiments 27 to 29, wherein,
[0273] The density of the solid catalyst mold is 1.26 g / cm³. 3 Up to 1.64 g / cm 3 .
[0274] 31. The solid catalyst molded body according to any one of embodiments 27 to 30, wherein,
[0275] The density of the solid catalyst mold is 1.28 g / cm³. 3 Up to 1.62 g / cm 3 .
[0276] 32. The solid catalyst molded body according to any one of embodiments 27 to 31, wherein,
[0277] The density of the solid catalyst mold is 1.30 g / cm³. 3 Up to 1.60 g / cm 3 .
[0278] 33. The solid catalyst molded body according to any one of embodiments 27 to 32, wherein,
[0279] The total pore volume of the solid catalyst mold is 0.34 cm³. 3 / g to 0.58cm 3 / g.
[0280] 34. A solid catalyst molded body according to any one of embodiments 27 to 33, wherein,
[0281] The total pore volume of the solid catalyst mold is 0.35 cm³. 3 / g to 0.56cm 3 / g.
[0282] 35. A solid catalyst molded body according to any one of embodiments 27 to 34, wherein,
[0283] The total pore volume of the solid catalyst mold is 0.36 cm³. 3 / g to 0.54cm 3 / g.
[0284] 36. A solid catalyst molded body according to any one of embodiments 27 to 35, wherein,
[0285] The total pore volume of the solid catalyst mold is 0.37 cm³. 3 / g to 0.52cm 3 / g.
[0286] 37. A solid catalyst molded body according to any one of embodiments 27 to 36, wherein,
[0287] The total pore volume of the solid catalyst mold is 0.38 cm³. 3 / g to 0.50cm 3 / g.
[0288] 38. A solid catalyst molded body according to any one of embodiments 27 to 37, wherein,
[0289] The pore volume of the solid catalyst molded body in the range of 0.1 μm to 1 μm is % of the total pore volume.
[0290] 86% to 98%.
[0291] 39. The solid catalyst molded body according to any one of embodiments 27 to 38, wherein,
[0292] The pore volume of the solid catalyst molded body in the range of 0.1 μm to 1 μm is % of the total pore volume.
[0293] 87% to 97%.
[0294] 40. A solid catalyst molded body according to any one of embodiments 27 to 39, wherein,
[0295] The pore volume of the solid catalyst molded body in the range of 0.1 μm to 1 μm is % of the total pore volume.
[0296] 88% to 96%.
[0297] 41. The solid catalyst molded body according to any one of embodiments 27 to 40, wherein,
[0298] The pore volume of the solid catalyst molded body in the range of 0.1 μm to 1 μm is % of the total pore volume.
[0299] 89% to 95%.
[0300] 42. The solid catalyst molded body according to any one of embodiments 27 to 41, wherein,
[0301] Cylindrical structure is
[0302] i) A cylindrical body with a continuous central circular opening in the longitudinal direction, or
[0303] ii) A three-fold concave cylindrical body having three circular continuous openings evenly arranged in the longitudinal direction.
[0304] 43. The solid catalyst molded body according to embodiment 42, wherein the shortest distance between the outer wall of the cylindrical body and the nearest continuous opening is 0.75 mm to 2.5 mm.
[0305] 44. The solid catalyst molded body according to embodiment 42 or 43, wherein the cylindrical main body
[0306] The shortest distance between the outer wall of the body and the nearest continuous opening is 0.8 mm to 2.0 mm.
[0307] 45. The solid catalyst molded body according to embodiment 42 or 44, wherein the cylindrical main body
[0308] The shortest distance between the outer wall of the body and the nearest continuous opening is 1.0 mm to 1.8 mm.
[0309] 46. The solid catalyst molded body according to embodiment 42 or 45, wherein the cylindrical main body
[0310] The shortest distance between the outer wall of the body and the nearest continuous opening is 1.2 mm to 1.7 mm.
[0311] 47. The solid catalyst molded body according to embodiment 42 or 46, wherein the cylindrical main body
[0312] The shortest distance between the outer wall of the body and the nearest continuous opening is 1.3 mm to 1.6 mm.
[0313] 48. A solid catalyst molded body according to any one of embodiments 27 to 42, wherein,
[0314] A cylindrical structure is a hollow cylinder.
[0315] 49. The solid catalyst molding body according to embodiment 48, wherein the wall thickness of the hollow cylinder is 0.75 mm to 2.5 mm.
[0316] 50. The solid catalyst molded body according to embodiment 48 or 49, wherein the wall thickness of the hollow cylinder is 0.8 mm to 2.0 mm.
[0317] 51. The solid catalyst molded body according to any one of embodiments 48 to 50, wherein,
[0318] The wall thickness of the hollow cylinder is 1.0 mm to 1.8 mm.
[0319] 52. The solid catalyst molded body according to any one of embodiments 48 to 51, wherein,
[0320] The wall thickness of the hollow cylinder is 1.2 mm to 1.7 mm.
[0321] 53. The solid catalyst molded body according to any one of embodiments 48 to 52, wherein,
[0322] The wall thickness of the hollow cylinder is 1.3 mm to 1.6 mm.
[0323] 54. A solid catalyst molded body according to any one of embodiments 27 to 53, wherein,
[0324] The solid catalyst molded body is a multi-component oxide of general formula I.
[0325] Mo 12 Bi a Fe b Co c Ni d X e Y f Z g O n (I)
[0326] in,
[0327] X = K, Cs and / or Rb
[0328] Y=Ca,Sr,Ba,Li,Na,Cr,W,Mn,Cu,Zn,Ga,P,B,As,Sn,Sb,Te,Nb,Ta,Pb,Ce and / or La
[0329] Z = Si, Al, Ti, Zr and / or Mg
[0330] a = 0.2 to 2
[0331] b = 1 to 4
[0332] c = 3 to 9
[0333] d = 0 to 4
[0334] c+d = 4 to 9.5
[0335] e = 0.01 to 0.5
[0336] f = 0 to 10
[0337] g = 0 to 10
[0338] n = a number determined by the valence and abundance of elements other than oxygen in general formula I.
[0339] 55. A method for preparing α,β-unsaturated aldehydes and / or α,β-unsaturated carboxylic acids, wherein, having
[0340] Olefins and / or alcohols containing molecular oxygen are passed through a catalyst fixed bed, which includes a solid catalyst molded body bed according to any one of embodiments 27 to 54.
[0341] 56. The method according to embodiment 55, wherein propylene is used as an olefin.
[0342] 57. A fixed-bed reactor comprising, according to any one of embodiments 27 to 55, a solid bed reactor.
[0343] Bulk catalyst molding bulk bed. Example
[0344] Preparation of solid catalyst molds K1 to K10:
[0345] Example 1
[0346] Preparation of solid catalyst precursor molding body K1, wherein the active multimetal oxide has a stoichiometric ratio of Mo 12 Co7Fe3Bi 0.6 Si 1.6 K 0.08 O x .
[0347] In each case, the mixing vessel is filled in the presence of ambient air. During stirring / mixing, it is hermetically sealed with a lid that has a pressure-reducing valve open to the atmosphere (1.01 bar).
[0348] a) Preparation of aqueous solution B
[0349] 430 kg of fully softened water is introduced into a 1.75 m stainless steel (EN 1.4541) temperature-controlled cylindrical mixing vessel equipped with a stirrer. 3 The contents were placed in a container with an internal volume of 1.3 m in diameter and heated to 60 °C with stirring (70 rpm).
[0350] Subsequently, under continuous stirring and at a temperature of 60°C, 0.61 kg of an aqueous solution of potassium hydroxide (47.5% by weight KOH) at 20°C was added over one minute. While maintaining 60°C, 136.2 kg of fine-particle ammonium heptamolybdate tetrahydrate (54.3% by weight Mo, supplier: NIPPON INORGANICCOLOUR & CHEMICAL CO., LTD., 3-14-1 Funado Itabashi-ku Tokyo 174-0041, Japan) was stirred in batches at a temperature of 25°C. The resulting aqueous solution (which exhibited slight turbidity due to the slightest insoluble polymolybdate impurities) was then stirred for another 60 minutes at 60°C (70 rpm).
[0351] b) Preparation of aqueous solution A
[0352] 212 kg of cobalt(II) nitrate aqueous solution (12.5 wt% Co, 27 wt% nitrate, prepared by dissolving cobalt metal from MFT Metals% Ferro-Alloys Trading GmbH, D-41474 Viersen, with a purity >99.6 wt% Co, <0.3 wt% Ni, <100 mg / kg Fe, <50 mg / kg Cu in nitric acid aqueous solution) was introduced into a 1.75 m stainless steel (EN 1.4541) temperature-controlled cylindrical stirred vessel equipped with a stirrer. 3 The contents were placed in a container with an internal volume of 1.3 m in diameter and heated to 60 °C with stirring (70 rpm).
[0353] While continuing stirring (70 rpm) and tempering to 60°C, 78 kg of ferric(III) nonhydrate melt heated at 60°C (13.8 wt% Fe, <0.4 wt% alkali metal, <0.01 wt% chloride, <0.02 wt% sulfate, from Dr. Paul Lohmann GmbH, D-81857Emmerthal) was weighed and stirred at 60°C (70 rpm) for another 30 minutes.
[0354] Add 72.6 kg of a bismuth nitrate aqueous solution (11.1 wt% Bi, 13 wt% nitrate, prepared by dissolving bismuth metal from Sidech SA, BE-1495Tilly, purity >99.997 wt% Bi, <7 mg / kg Pb, <5 mg / kg each of Ni, Ag, Fe, <3 mg / kg each of Cu, Sb, and <1 mg / kg each of Cd and Zn in nitric acid aqueous solution) to the obtained aqueous solution, while maintaining 60°C and continuing stirring (70 rpm), and then stirring for another 30 minutes at 60°C (70 rpm).
[0355] c) Mix aqueous solution A with aqueous solution B
[0356] Aqueous solution A, heated to 60°C, was continuously metered into aqueous solution B, which was stirred vigorously (70 rpm) at 60°C, over 15 minutes. The resulting aqueous suspension was then stirred at 60°C for another 15 minutes.
[0357] d) Adding silica sol yields an aqueous mixture M
[0358] Immediately after stirring, add 12.6 kg of TM50 silica gel (47.5% by weight SiO2) heated to 60°C from Grace GmbH & KG, In der Hollerecke 1, D-67545Worms to the aqueous mixture obtained in c).
[0359] e) Spray drying of aqueous mixture M
[0360] The aqueous mixture M was spray-dried immediately after preparation. In each case, the aqueous mixture (suspension) M, further stirred by a stirrer (40 rpm) at 60°C (also during spray drying), was spray-dried in a spray tower (S-50-N / R type from Niro A / S, made of stainless steel 1.4541), equipped with an FS-15 type centrifugal atomizer and an AM8-150 type atomizer wheel (gas inlet temperature: 350±10°C, gas outlet temperature: 140±5°C, gas flow rate: 2200±100 Nm). 3 / h, atomizer wheel speed: 20000rpm).
[0361] The obtained spray powder was temporarily stored in an airtight container (200 L or 1000 L internal volume, 25 °C, atmospheric pressure) until further processing (10 calendar days; shorter or longer temporary storage (maximum 30 calendar days) had no effect on the results). The annealing loss of the obtained spray powder (annealed at 600 °C (powder temperature) in excess air for 3 hours) was 31 ± 2% of its initial weight. At an absolute dispersion pressure of 2.0 bar, the D50 of the spray powder was 35 ± 10 μm (D50 represents 50% of the particles smaller than the specified value).
[0362] f) Preparation of the annular precursor mold
[0363] Then 100 kg of spray powder and 1 kg of graphite (from Asbury Graphite Mills Inc., New Jersey 08802, Class 3160) were introduced into an inclined layer mixer (VIL type, fill volume: 200 l, Aachener Misch- und Knetmaschinenfabrik) with mixing and cutting blades (mixing blade speed: 39 rpm, cutting blade speed: 3000 rpm) and premixed for 5 minutes.
[0364] The resulting mixture was then compacted in a K200 / 100 compactor from Hosokawa Bepex GmbH, which features grooved smooth rollers (roller diameter 100 mm, roller length 200 mm, gap width: 2.8 mm, roller speed: 5 rpm, pressure setting: 80 kN, length-to-pressure setting: 8 kN / cm). The compacted material, primarily with particle sizes between 200 μm and 1.5 mm, was separated using an integrated vibrating screen from Allgaier (excess screen width: 1.5 mm, minimum screen width: 200 μm) and a spherical sieve aid (diameter 22 mm).
[0365] For tableting, an additional 2.5% by weight of graphite (Grade 3160, from Asbury Graphite Mills Inc., New Jersey 08802) is mixed into the compact within 2 minutes in a turbulent mixer from Drais.
[0366] Subsequently, the generated granules are compressed (tableted) in a dry air atmosphere using a Korsch XT-600 rotator (with a 65EURO B matrix) to form an annular precursor molded body with a geometry of A×H×I=5mm×5mm×2mm, having non-curved (i.e., flat) end faces, and a mass (M vThe applied pre-compression force (compression force) was 0.7 kN, and the applied main compression force (compression force) was 2.7 kN. The rotor speed was 40 rpm. The lateral compressive strength (SDF) of the resulting annular precursor molded body was... V ) is 23N.
[0367] Heat pretreatment and calcination of the annular precursor molded body prepared in g)f)
[0368] The molded ring is placed on the belt of a belt calcining apparatus (as described in WO 2002 / 024620) having eight chambers (chamber width 100cm, chamber length 150cm).
[0369] Chambers 1 to 8 each have a fan for generating air circulation, and the temperatures are controlled at 150°C, 190°C, 220°C, 265°C, 380°C, 430°C, 520°C, and 520°C, respectively. Heated air is metered into each chamber. The air supply to chambers 1 to 8 is 90 Nm³, respectively. 3 / h, 130Nm 3 / h, 255Nm 3 / h、90Nm 3 / h, 150Nm 3 / h、90Nm 3 / h、90Nm 3 / h and 140Nm 3 / h. Exhaust gas is discharged from each chamber via a fan. The exhaust gas volume from chambers 1 to 8 is 130 Nm³. 3 / h, 290Nm 3 / h, 305Nm 3 / h、144Nm 3 / h, 135Nm 3 / h, 80Nm 3 / h, 80Nm 3 / h and 130Nm 3 / h.
[0370] The pouring height for chambers 1 to 4 is 40 mm. The pouring height for chambers 5 to 8 is 75 mm. Within the chambers, the temporal and spatial deviations from the target temperature are consistently ≤10℃.
[0371] The conveyor belt speed results in a dwell time of 105 minutes in the first four chambers and 270 minutes in the fifth through eighth chambers.
[0372] In this manner, 2.6 t of solid catalyst molded body K1 was prepared.
[0373] Example 2 (not based on the present invention)
[0374] Preparation of solid catalyst mold K2, wherein the active multimetal oxide has a stoichiometric ratio of Mo 12 Co7Fe3Bi 0.6 Si 1.6 K 0.08 O x .
[0375] The preparation of solid catalyst mold K2 is the same as that of solid catalyst mold K1, and it is modified in f).
[0376] The precursor molding is compressed (tableted) to a mass of 220 mg (M). v The applied pre-compression force (compression force) was 1.3 kN, and the applied main compression force (compression force) was 6.8 kN. The lateral compressive strength (SDF) of the resulting annular precursor molded body... V The value is 48N.
[0377] Example 3
[0378] Preparation of solid catalyst mold K3, wherein the active polymetallic oxide has a stoichiometric ratio of Mo 12 Co7Fe3Bi 0.6 Si 1.6 K 0.08 O x .
[0379] The preparation of solid catalyst molded body K3 is the same as that of solid catalyst molded body K1, and it has the modifications described in f) and g).
[0380] In f), the generated particles are compressed (tableted) in a dry air atmosphere using a Kilian E150+ rotator (with a 21 EURO D matrix) to form an annular precursor molded body with a geometry of A×H×I=5mm×3mm×2mm, having non-curved (i.e., flat) end faces, and a mass (M V The value was 90 mg. The rotor speed was 25 rpm. The lateral compressive strength (SDF) of the resulting annular precursor molded body was... V The value is 6N.
[0381] 1000g of the precursor molded body prepared in f) was uniformly distributed on four side-by-side grids, each grid having a base surface of 150mm × 150mm (pouring height: 15mm), and placed in a circulating air shaft furnace (Nabertherm GmbH, D-28865 Lilienthal; furnace model S60 / 65A), which was dried at a rate of 4500 Nl / h (inlet temperature 140°C) with the airflow flowing through it (the circulating air furnace was located in an environment of 25°C). Subsequently, while maintaining the airflow (including its inlet temperature), the temperature changes in the circulating air shaft furnace were as follows (temperature data represent the temperature in the corresponding applied bulk material; this was determined by four thermocouples, each located at the geometric center of the four grids at the center of the bulk material applied to the corresponding grid; one thermocouple provides the actual value for temperature control of the circulating air shaft furnace; the other thermocouples confirm that the temperature is the same within ±0.1°C). The temperature increase was substantially linear over time. Heat the mixture from 25°C to 130°C over 72 minutes. Hold at 130°C for 72 minutes, then increase the temperature to 190°C over 36 minutes.
[0382] The temperature was held at 190°C for 72 minutes, then increased to 220°C over 36 minutes. It was held at 220°C for 72 minutes, then increased to 265°C over 36 minutes. It was held at 265°C for 72 minutes, then increased to 380°C over 93 minutes. It was held at 380°C for 187 minutes, then increased to 430°C over 93 minutes. It was held at 430°C for 187 minutes, then increased to the final calcination temperature of 500°C over 93 minutes. This was maintained for 463 minutes. The mixture was then cooled to 25°C over 12 hours. For this purpose, the heating of the circulating air shaft furnace and the gas flow preheating were shut off (however, the gas flow itself of 4500 Nl / h remained constant; the gas flow inlet temperature was 25°C).
[0383] Example 4 (not based on the present invention)
[0384] Preparation of solid catalyst mold K4, wherein the active multimetal oxide has a stoichiometric ratio of Mo 12 Co7Fe3Bi 0.6 Si 1.6 K 0.08 O x .
[0385] The preparation of solid catalyst molded body K4 is the same as that of solid catalyst molded body K3, and it is modified in f).
[0386] The precursor molding is compressed (tableted) to a mass of 122 mg (M). v The lateral compressive strength (SDF) of the resulting annular precursor molded body. V) is 22N.
[0387] Example 5
[0388] Preparation of solid catalyst mold K5, wherein the active polymetallic oxide has a stoichiometric ratio of Mo 12 Co 8.3 Fe 2.1 Bi 0.6 Si 1.6 K 0.08 O x .
[0389] In each case, the mixing vessel is filled in the presence of ambient air. During stirring / mixing, it is hermetically sealed with a lid that has a pressure-reducing valve open to the atmosphere (1.01 bar).
[0390] a) Preparation of aqueous solution B
[0391] 654 kg of fully softened water was introduced into a 1.75 m stainless steel (EN 1.4541) temperature-controlled cylindrical mixing vessel equipped with a stirrer. 3 The contents were placed in a container with an internal volume of 1.3 m in diameter and heated to 60 °C with stirring (70 rpm).
[0392] Subsequently, under continuous stirring and at a temperature of 60°C, 0.36 kg of an aqueous solution of potassium hydroxide (47.5% by weight KOH) at 20°C was added over one minute. While maintaining 60°C, 80.4 kg of fine-particle ammonium heptamolybdate tetrahydrate (54.3% by weight Mo, supplier: NIPPON INORGANICCOLOUR & CHEMICAL CO., LTD., 3-14-1 Funado Itabashi-ku Tokyo 174-0041 Japan) was stirred in batches at 25°C, and then the resulting aqueous solution (which exhibited slight turbidity due to the slightest insoluble polymolybdate impurities) was stirred at 60°C (70 rpm) for 60 minutes.
[0393] b) Preparation of aqueous solution A
[0394] 148.4 kg of cobalt(II) nitrate aqueous solution (12.5 wt% Co, 27 wt% nitrate, prepared by dissolving cobalt metal from MFT Metals% Ferro-Alloys Trading GmbH, D-41474 Viersen, with a purity >99.6 wt% Co, <0.3 wt% Ni, <100 mg / kg Fe, <50 mg / kg Cu in nitric acid aqueous solution) was introduced into a 1.75 m stainless steel (EN 1.4541) temperature-controlled cylindrical stirred vessel equipped with a stirrer. 3 The contents were placed in a container with an internal volume of 1.3 m in diameter and heated to 60 °C with stirring (70 rpm).
[0395] While continuing stirring (70 rpm) and tempering to 60°C, 32.3 kg of ferric(III) nonhydrate melt heated at 60°C (13.8 wt% Fe, <0.4 wt% alkali metal, <0.01 wt% chloride, <0.02 wt% sulfate, from Dr. Paul Lohmann GmbH, D-81857Emmerthal) was weighed and stirred at 60°C (70 rpm) for another 30 minutes.
[0396] Add 42.8 kg of a bismuth nitrate aqueous solution (11.1% by weight Bi, 13% by weight nitrate) heated at 60°C to the obtained aqueous solution. 3- Bismuth metal was prepared by dissolving Bi from Sidech SA, BE-1495 Tilly, with a purity >99.997% by weight (Bi, <7 mg / kg), Pb, <5 mg / kg each of Ni, Ag, Fe, <3 mg / kg each of Cu, Sb, and <1 mg / kg each of Cd and Zn in an aqueous nitric acid solution, while maintaining 60°C and continuing stirring (70 rpm), and then stirring for another 30 minutes at 60°C (70 rpm).
[0397] c) Mix aqueous solution A with aqueous solution B
[0398] Aqueous solution A, heated to 60°C, was continuously metered into aqueous solution B, which was stirred vigorously (70 rpm) at 60°C, over 15 minutes. The resulting aqueous suspension was then stirred at 60°C for another 15 minutes.
[0399] d) Adding silica sol yields an aqueous mixture M
[0400] Immediately after stirring, add 7.4 kg of TM50 silica gel (47.5% by weight SiO2) heated to 60°C from Grace GmbH & KG, In der Hollerecke 1, D-67545 Worms to the aqueous mixture obtained in c).
[0401] e) Spray drying of aqueous mixture M
[0402] The aqueous mixture M was spray-dried immediately after preparation. In each case, the aqueous mixture (suspension) M, further stirred by a stirrer (40 rpm) at 60°C (also during spray drying), was spray-dried in a spray tower (S-50-N / R type from Niro A / S, made of stainless steel 1.4541) under direct hot air (gas inlet temperature: 350±10°C, gas outlet temperature: 140±5°C, airflow intensity: 2200±100 Nm). 3 / h, atomizer wheel speed: 20000rpm).
[0403] The obtained spray powder was temporarily stored in an airtight container (200 L or 1000 L internal volume, 25 °C, atmospheric pressure) until further processing (10 calendar days; shorter or longer temporary storage (maximum 30 calendar days) had no effect on the results). The annealing loss of the obtained spray powder (annealed at 600 °C (powder temperature) in excess air for 3 hours) was 31 ± 2% of its initial weight. At an absolute dispersion pressure of 2.0 bar, the D50 of the spray powder was 35 ± 10 μm (D50 represents 50% of the particles smaller than the specified value).
[0404] f) Preparation of the annular precursor mold
[0405] Then 100 kg of spray powder and 1 kg of graphite (from Asbury Graphite Mills Inc., New Jersey 08802, Class 3160) were introduced into an inclined layer mixer (VIL type, fill volume: 200 l, Aachener Misch- und Knetmaschinenfabrik) with mixing and cutting blades (mixing blade speed: 39 rpm, cutting blade speed: 3000 rpm) and premixed for 5 minutes.
[0406] The resulting mixture was then compacted in a K200 / 100 compactor from Hosokawa Bepex GmbH, which features grooved smooth rollers (roller diameter 100 mm, roller length 200 mm, gap width: 2.8 mm, roller speed: 5 rpm, pressure setting: 80 kN, length-to-pressure setting: 8 kN / cm). The compacted material, primarily with particle sizes between 200 μm and 1.5 mm, was separated using an integrated vibrating screen from Allgaier (excess screen width: 1.5 mm, minimum screen width: 200 μm) and a spherical sieve aid (diameter 22 mm).
[0407] For tableting, an additional 2.5% by weight of graphite (Grade 3160, from Asbury Graphite Mills Inc., New Jersey 08802) is mixed into the compact within 2 minutes in a turbulent mixer from Drais.
[0408] Subsequently, the granules produced as described above are compressed (tableted) in a dry air atmosphere using a Kilian E150+ rotator (with a 21 EURO D matrix) to form an annular precursor molded body with a geometry of A×H×I=5mm×3mm×2mm, having non-curved (i.e., flat) end faces, and a mass (M V The value was 102 mg. The rotor speed was 25 rpm. The lateral compressive strength (SDF) of the resulting annular precursor molded body was... V ) is 12N.
[0409] Heat pretreatment and calcination of the annular precursor molded body prepared in g)f)
[0410] 1000g of the prepared precursor molding was evenly distributed on four side-by-side grids, each with a base surface of 150mm × 150mm (pouring height: 15mm), and placed in a circulating air shaft furnace (Nabertherm GmbH, D-28865 Lilienthal; furnace model S60 / 65A), which was dried at a rate of 4500 Nl / h (inlet temperature 140°C) with the airflow flowing through it (the circulating air furnace was located in an environment of 25°C). Subsequently, while maintaining the airflow (including its inlet temperature), the temperature changes in the circulating air shaft furnace were as follows (temperature data represent the temperature of the corresponding applied bulk material; this was determined by four thermocouples, each located at the geometric center of the four grids at the center of the bulk material applied to the corresponding grid; one thermocouple provides the actual value for temperature control of the circulating air shaft furnace; the other thermocouples confirm that the temperature is the same within ±0.1°C). The temperature increase was substantially linear over time. The mixture was heated from 25°C to 130°C within 72 minutes. The temperature was held at 130°C for 72 minutes, then increased to 190°C over 36 minutes. It was held at 190°C for 72 minutes, then increased to 220°C over 36 minutes. It was held at 220°C for 72 minutes, then increased to 265°C over 36 minutes. It was held at 265°C for 72 minutes, then increased to 380°C over 93 minutes. It was held at 380°C for 187 minutes, then increased to 430°C over 93 minutes. It was held at 430°C for 187 minutes, then increased to the final calcination temperature of 500°C over 93 minutes. This was maintained for 463 minutes. The mixture was then cooled to 25°C over 12 hours. For this purpose, the heating of the circulating air shaft furnace and the gas flow preheating were shut off (however, the gas flow itself of 4500 Nl / h remained constant; the inlet temperature of the gas flow was 25°C).
[0411] Example 6 (not based on the present invention)
[0412] Preparation of solid catalyst mold K6, wherein the active multimetal oxide has a stoichiometric ratio of Mo 12 Co 8.3 Fe 2.1 Bi 0.6 Si 1.6 K 0.08 O x .
[0413] The preparation of solid catalyst molded body K6 is the same as that of solid catalyst molded body K5, and it is modified in f).
[0414] The precursor molding was compressed (tableted) to a mass of 119 mg (M). v The lateral compressive strength (SDF) of the resulting annular precursor molded body. V The value is 26N.
[0415] Example 7
[0416] Preparation of solid catalyst mold K7, wherein the active multimetal oxide has a stoichiometric ratio of Mo 12 Co 8.3 Fe 2.1 Bi 0.6 Si 1.6 K 0.08 O x .
[0417] The preparation of solid catalyst molded body K7 is the same as that of solid catalyst molded body K5, and it is modified in f).
[0418] In f), the generated particles are compressed (tableted) in a dry air atmosphere using a Korsch PH 865 rotator (with 65 substrates) to obtain an annular precursor molded body with a geometry of A×H×I=5mm×5mm×2mm, having non-curved (i.e., flat) end faces, and a mass (M V The lateral compressive strength (SDF) of the resulting annular precursor molded body was 166 mg. The rotor speed was 40 rpm. V The value is 10N.
[0419] Example 8
[0420] Preparation of solid catalyst mold K8, wherein the active multimetal oxide has a stoichiometric ratio of Mo 12 Co 8.3 Fe 2.1 Bi 0.6 Si 1.6 K 0.08 O x .
[0421] The preparation of solid catalyst molded body K8 is the same as that of solid catalyst molded body K7, and it is modified in f).
[0422] The precursor molding is compressed (tableted) to a mass of 185 mg (M). v The lateral compressive strength (SDF) of the resulting annular precursor molded body. V The value is 16N.
[0423] Example 9 (not based on the present invention)
[0424] Preparation of solid catalyst mold K9, wherein the active multimetal oxide has a stoichiometric ratio of Mo 12 Co 8.3 Fe 2.1 Bi 0.6 Si1.6 K 0.08 O x .
[0425] The preparation of solid catalyst molded body K9 is the same as that of solid catalyst molded body K7, and it is modified in f).
[0426] The precursor molding is compressed (tableted) to a mass of 205 mg (M). v The lateral compressive strength (SDF) of the resulting annular precursor molded body. V The value is 26N.
[0427] Example 10 (not based on the present invention)
[0428] A solid catalyst mold K10 was prepared, wherein the active multimetal oxide has a stoichiometric ratio of [Bi₂W₂O₉₂WO₃]. 0.40 x[Mo 12 Co 5.4 Fe 3.1 Si 1.5 K 0.08 O x ]1.
[0429] According to WO 2010 / 000720 Example I. Preparation of solid catalyst mold K10.
[0430] The mass (M) of a ring-shaped precursor molded body with a geometry of A×H×I = 5mm×5mm×2mm and a non-curved (i.e., flat) end face is... V The value is 129mg.
[0431] Testing of cyclic solid catalysts K1 to K10 used for the heterogeneous catalytic partial oxidation of propylene to acrolein and acrylic acid:
[0432] The reaction tube (1.4541 stainless steel (EU standard EN 10088-3); outer diameter 33.7 mm; wall thickness 2 mm; inner diameter 29.7 mm; length 400 mm; 4 mm heat sleeve) is used for solid catalyst molding bodies K1 to K6.
[0433] For solid catalyst molding bodies K7 to K10, a reaction tube (1.4541 stainless steel (EU standard EN10088-3); outer diameter 30 mm; wall thickness 2 mm; inner diameter 26 mm; length 400 mm, without heating sleeve) is used.
[0434] The corresponding reaction tubes are loaded from bottom to top as follows:
[0435] Part 1: Length 60cm
[0436] Prefilled with talc rings (outer diameter × length × inner diameter; C220 talc from CeramTec) with a geometry of 7mm × 3mm × 4mm;
[0437] Reaction Zone: Consists of two parts (see Table 3; Zone 1 is closest to the reactor inlet).
[0438] Part 2: Length 30cm
[0439] Fill with the same talc ring as in part 1;
[0440] Part 3: Empty Pipe
[0441] The structure of the reaction zone is shown in Table 3. To set the relative volumetric catalyst activity, solid catalyst molds were diluted with inert talc rings with a geometry of 5 mm × 3 mm × 2 mm (outer diameter × length × inner diameter, C220 talc from CeramTec) or a geometry of 5 mm × 5 mm × 2 mm (outer diameter × length × inner diameter, C220 talc from CeramTec).
[0442] A mixture of reactant gases having the following contents flows from top to bottom through the corresponding reaction tube loaded as described above:
[0443] Propylene content ranging from 5.8% to 6.4% by volume.
[0444] 1.5 to 3% by volume H2O
[0445] CO from 0.2% to 0.5% by volume,
[0446] CO2 from 0.6% to 1.0% by volume,
[0447] Acrolein at concentrations ranging from 0.02% to 0.05% by volume.
[0448] O2 and 10.2% to 11.7% by volume
[0449] The remaining amount is 100% molecular nitrogen.
[0450] In each case, a salt bath (a mixture of 53 wt% potassium nitrate, 40 wt% sodium nitrite, and 7 wt% sodium nitrate; 50 kg molten salt) was stirred and electrically heated from the outside, and flushed along the length of the reaction tube at a flow rate of 3 m / s. 3 / h (in a plane perpendicular to the longitudinal axis of the pipe).
[0451] Temperatures in the catalyst beds of solid catalysts K1 to K6 were continuously measured using thermocouples placed in heated sleeves within the reactor tubes and propelled upwards from the bottom of the reactor bed by a traction device. The highest temperature measured corresponded to the hot spot temperature T. H .
[0452] The drop test described in this paper is as follows:
[0453] A 50g solid catalyst mold was dropped through a 3.5m long vertical tube with an inner diameter of 23mm. The solid catalyst mold landed in a ceramic dish directly below the tube and separated from the dust and debris generated during the impact. The solid catalyst mold separated from the dust and debris was weighed. The proportion of broken solid catalyst mold was determined by comparing the measured mass with the mass of the solid catalyst mold used. The proportion of broken solid catalyst mold is a measure of the mechanical resistance of the solid catalyst mold.
[0454] In this literature, the selectivity (S (molar percentage)) in the formation of valuable products is understood as:
[0455]
[0456] (In each case, the conversion rate is based on the reaction gas mixture passing through the catalyst fixed bed in a single pass).
[0457] each Example Comparison of E1 / E2, E3 / E4, and E5 / E6, and Example E7 and E8 Example A comparison of E9 and E10 shows that the solid catalyst molded body according to the present invention has significantly higher selectivity for valuable products and significantly higher yield of valuable products (with lower catalyst mass). Meanwhile, the solid catalyst molded body according to the present invention has sufficient mechanical stability.
[0458]
[0459]
[0460]
[0461]
Claims
1. A method for producing a solid catalyst molded body for gas phase oxidation of olefins and / or alcohols to α,β-unsaturated aldehydes and / or α,β-unsaturated carboxylic acids, wherein: The solid catalyst molded body contains at least the elements molybdenum, bismuth, iron and cobalt, wherein: a) an aqueous solution or aqueous suspension is produced from each of at least one source of the elemental components molybdenum, bismuth, iron, cobalt and optionally at least one source of the elemental component nickel, b) producing a powder P by drying the aqueous solution or aqueous suspension obtained in a) and optionally comminuting, c) the powder P obtained in b), optionally with the addition of one or more auxiliaries and after homogeneous mixing and optionally compacting, is compacted into a precursor molding having a cylindrical structure, and d) heat-treating the precursor molded body obtained in c) to form the solid catalyst molded body, Characterized in that the pressure during the pressing in c) is selected so that the density of the precursor molded body is 1.70 g / cm 3 Up to 2.30g / cm 3 , wherein the density of the precursor molded body is the quotient of mass and geometric volume, and the weight loss during the heat treatment in d) is 25 weight percent to 40 weight percent.
2. The method according to claim 1, characterized in that: The cylindrical structure is i) a cylindrical body having a central circular continuous opening in the longitudinal direction, or ii) A 3-fold notched cylindrical body having three circular continuous openings uniformly arranged in the longitudinal direction.
3. The method according to claim 1 or 2, characterized in that: The molybdenum content of the solid catalyst molded body, calculated as MoO3, is 45% by weight to 75% by weight.
4. The method according to any one of claims 1 to 3, characterized in that The bismuth content of the solid catalyst molded body, calculated as Bi2O3, is 1 weight percent to 20 weight percent.
5. The method according to any one of claims 1 to 4, characterized in that The iron content of the solid catalyst molded body, calculated as Fe2O3, is 2 to 12 weight percent.
6. The method according to any one of claims 1 to 5, characterized in that The cobalt and nickel contents of the solid catalyst molded body, calculated as CoO and NiO, are in a total of 9 to 30 weight percent.
7. A solid catalyst molded body having a cylindrical structure for gas phase oxidation of olefins and / or alcohols to α,β-unsaturated aldehydes and / or α,β-unsaturated carboxylic acids, obtainable by the method according to any one of claims 1 to 6, wherein: The solid catalyst molded body contains at least the elements molybdenum, bismuth, iron and cobalt, wherein the density of the solid catalyst molded body is 1.20 g / cm 3 Up to 1.70g / cm 3 , wherein the density of the solid catalyst molded body is the quotient of mass and geometric volume, and the total pore volume of the solid catalyst molded body is 0.33 cm 3 / g to 0.60cm 3 / g, and the pore volume of the solid catalyst molded body in the range of 0.1 μm to 1 μm is 85% to 99% of the total pore volume, wherein the total pore volume and the pore volume in the range of 0.1 μm to 1 μm are determined by mercury porosimetry.
8. The solid catalyst molded body according to claim 7, characterized in that The cylindrical structure is i) a cylindrical body having a central circular continuous opening in the longitudinal direction, or ii) A 3-fold notched cylindrical body having three circular continuous openings uniformly arranged in the longitudinal direction.
9. The solid catalyst molded body according to claim 8, wherein The shortest distance between the outer wall of the cylindrical body and the nearest continuous opening is 0.75 mm to 2.5 mm.
10. The solid catalyst molded body according to any one of claims 7 to 9, wherein The density of the solid catalyst molded body is 1.35 g / cm 3 Up to 1.55g / cm 3 .
11. The solid catalyst molded body according to any one of claims 7 to 10, wherein The total pore volume of the solid catalyst molded body is 0.36 cm 3 / g to 0.45cm 3 / g.
12. The solid catalyst molded body according to any one of claims 7 to 11, wherein The solid catalyst molded body according to any one of claims 7 to 9, wherein the pore volume of the solid catalyst molded body in the range of 0.1 μm to 1 μm is 88% to 96% of the total pore volume.
13. A method for preparing an α,β-unsaturated aldehyde and / or an α,β-unsaturated carboxylic acid, wherein: The olefin and / or alcohol with molecular oxygen is passed through a catalyst fixed bed comprising a bed of solid catalyst molded bodies according to any one of claims 7 to 12.
14. The method according to claim 13, characterized in that Propylene was used as olefin.
15. A fixed bed reactor comprising a bed of a solid catalyst molded body according to any one of claims 7 to 12.
Citation Information
Patent Citations
Process for preparing a multimetal oxide catalyst, process for preparing unsaturated aldehydes and / or carboxylic acids and belt calcining device
DE10046957A1
Production of catalyst with shell of catalytically-active oxide used e.g. in gas phase oxidation of propene to acrolein uses support with ring geometry
DE10049873A1
Process for producing a multi-element oxide composition containing the element iron in oxidic form
DE102007003076A1
Preparing a catalyst molded body, useful e.g. to prepare catalyst for gas phase partial oxidation of an organic compound, comprises molding a precursor mixture to a desired geometry, using graphite, and thermally treating the molded body
DE102007004961A1
Preparing catalyst molded body comprises adding a finely ground precursor mixture to the graphite until the desired geometry is formed, thermally treating the catalyst precursor molded body to obtain the catalyst molded body
DE102007005606A1